Magnetic particle-containing composition, magnetic particle-containing film and electronic component

JP2024112858A5Active Publication Date: 2025-02-18FUJIFILM CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024077238
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-02-05
Filing Date
2024-05-10
Publication Date
2025-02-18
Estimated Expiration
2041-01-07

AI Technical Summary

Technical Problem

Existing magnetic particle-containing compositions face challenges in achieving both excellent sedimentation stability and magnetic permeability, particularly in forming magnetic particle-containing films for electronic components.

Method used

A magnetic particle-containing composition is developed with magnetic particles having a plurality of peak tops in a particle size distribution curve, a resin, and a solvent, where the ratio of the largest to smallest particle sizes is greater than 2, and the composition includes a resin with specific functional groups for improved dispersibility.

Benefits of technology

The composition achieves a magnetic particle-containing film with enhanced sedimentation stability and magnetic permeability, suitable for use in electronic components such as inductors and antennas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide a magnetic particle-containing composition which enables formation of a magnetic particle-containing film excellent in magnetic permeability, and is excellent in sedimentation stability, a magnetic particle-containing film formed using the magnetic particle-containing composition, and an electronic component containing the magnetic particle-containing film.SOLUTION: A magnetic particle-containing composition contains magnetic particles having a plurality of peak tops Pmax and Pmin in a particle size distribution curve indicating volume-based frequency distribution, a resin, and a solvent.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a magnetic particle-containing composition, a magnetic particle-containing film, and an electronic component. [Background technology]

[0002] In electronic communication devices, etc., electronic components using magnetic materials are used from the viewpoints of noise reduction, energy efficiency improvement, etc. Conventionally, a composition containing soft magnetic metal powder and resin is filled into a mold, and the composition is cured to obtain a magnetic composite material. A coil is then wound around the magnetic composite material, and the obtained inductor is mounted on a printed wiring board. However, due to the recent demand for miniaturization of electronic components, a method of forming a coil by a conductor pattern of a printed wiring board and providing an inductor inside the printed wiring board may be adopted. In the manufacture of such electronic components such as inductors, for example, Patent Document 1 discloses the use of a paste composition (magnetic particle-containing composition) containing magnetic inorganic particles (magnetic particles), a compound having a function of dispersing the magnetic inorganic particles, a resin, and an organic solvent. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2009-263645 A Summary of the Invention [Problem to be solved by the invention]

[0004] The inventors prepared a magnetic particle-containing composition containing magnetic particles, a resin, and a solvent with reference to Patent Document 1, and found that there is room for improvement, as it may be difficult to achieve both excellent sedimentation stability of the magnetic particles in the magnetic particle-containing composition (i.e., the magnetic particles are less likely to settle) and excellent magnetic permeability of the magnetic particle-containing film obtained using the magnetic particle-containing composition.

[0005] Therefore, an object of the present invention is to provide a magnetic particle-containing composition capable of forming a magnetic particle-containing film having excellent magnetic permeability and excellent sedimentation stability. Another object of the present invention is to provide a magnetic particle-containing film formed using the magnetic particle-containing composition, and an electronic component including the magnetic particle-containing film. [Means for solving the problem]

[0006] As a result of intensive research aimed at solving the above-mentioned problems, the inventors have discovered that a magnetic particle-containing composition containing magnetic particles having multiple peak tops in a particle size distribution curve representing a volume-based frequency distribution, a resin, and a solvent has excellent sedimentation stability, and a magnetic particle-containing film formed using the same has excellent magnetic permeability, thereby completing the present invention. That is, the present inventors have found that the above problems can be solved by the following configuration.

[0007] [1] A magnetic particle-containing composition comprising magnetic particles having multiple peak tops in a particle size distribution curve that represents a volume-based frequency distribution, a resin, and a solvent. [2] Among the plurality of peak tops in the particle size distribution curve representing the volume-based frequency distribution, the particle diameter at the peak top Pmin having the smallest particle diameter is defined as Dmin, and the particle diameter at the peak top Pmax having the largest particle diameter is defined as Dmax. The magnetic particle-containing composition according to [1], wherein the ratio of the Dmax to the Dmin is greater than 2. [3] When the particle diameter at the peak top Pmin having the smallest particle diameter among the plurality of peak tops in the particle size distribution curve representing the volume-based frequency distribution is defined as Dmin, The above Dmin is the particle diameter D when the frequency in the particle size distribution curve representing the cumulative distribution on a volume basis is 20%. 20 The magnetic particle-containing composition according to [1] or [2] above. [4] The magnetic particle-containing composition according to [2] or [3], wherein the Dmin is 1 to 10 μm. [5] The magnetic particle-containing composition according to any one of [1] to [4], wherein the magnetic particles have two peak tops. [6] The magnetic particle-containing composition according to any one of [1] to [5], wherein the content of the magnetic particles is 60 mass % or more based on the total mass of the magnetic particle-containing composition. [7] The magnetic particle-containing composition according to any one of [1] to [6], wherein the resin has an acid group, a basic group or an amide group. [8] The magnetic particle-containing composition according to any one of [1] to [7], wherein the solubility of the resin in the solvent is 10 g / L or more. [9] A magnetic particle-containing film formed by using the magnetic particle-containing composition according to any one of [1] to [8].

[10] An electronic component comprising the magnetic particle-containing film according to [9].

[11] The electronic component according to

[10] , which is used as an inductor.

[12] The electronic component according to

[10] , which is used as an antenna. Effect of the Invention

[0008] According to the present invention, it is possible to form a magnetic particle-containing film having excellent magnetic permeability and to provide a magnetic particle-containing composition having excellent sedimentation stability. The present invention also provides a magnetic particle-containing film formed using the magnetic particle-containing composition, and an electronic component including the magnetic particle-containing film. [Brief description of the drawings]

[0009] [Figure 1] FIG. 2 is a particle size distribution diagram showing an example of a particle size distribution curve showing a volume-based frequency distribution of magnetic particles contained in the composition of the present invention. [Diagram 2] FIG. 2 is a particle size distribution diagram showing an example of a particle size distribution curve showing a volume-based cumulative distribution of magnetic particles contained in the composition of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described in detail below. The following description of the components may be based on a representative embodiment of the present invention, but the present invention is not limited to such an embodiment. In the present specification, the notation of groups (atomic groups) that does not indicate whether they are substituted or unsubstituted includes both unsubstituted and substituted groups, unless it is contrary to the spirit of the present invention. For example, an "alkyl group" includes not only an alkyl group that does not have a substituent (unsubstituted alkyl group), but also an alkyl group that has a substituent (substituted alkyl group). In addition, an "organic group" in the present specification refers to a group that contains at least one carbon atom.

[0011] In this specification, "actinic rays" or "radiation" refers to, for example, the bright line spectrum of a mercury lamp, far ultraviolet light represented by an excimer laser, extreme ultraviolet light (EUV light: extreme ultraviolet), X-rays, and electron beams (EB), etc. In this specification, "light" refers to actinic rays or radiation. In this specification, unless otherwise specified, "exposure" includes not only exposure to the emission line spectrum of a mercury lamp, far ultraviolet light represented by an excimer laser, extreme ultraviolet light, X-rays, EUV light, and the like, but also drawing with particle beams such as electron beams and ion beams.

[0012] In this specification, the symbol "to" is used to mean that the numerical values ​​before and after it are included as the lower limit and upper limit.

[0013] In this specification, (meth)acrylate refers to acrylate and methacrylate, (meth)acrylic refers to acrylic and methacrylic, and (meth)acryloyl refers to acryloyl and methacryloyl.

[0014] In this specification, the "total solid content" of a magnetic particle-containing composition means the components that form a magnetic particle-containing film, and when the magnetic particle-containing composition contains a solvent (organic solvent, water, etc.), it means all components excluding the solvent. In addition, liquid components are also considered to be solids if they form a magnetic particle-containing film.

[0015] In this specification, the weight average molecular weight (Mw) is a value calculated as polystyrene by the GPC (Gel Permeation Chromatography) method. In this specification, the GPC method is based on a method using HLC-8020GPC (manufactured by Tosoh Corporation), TSKgel SuperHZM-H, TSKgel SuperHZ4000, and TSKgel SuperHZ2000 (manufactured by Tosoh Corporation, 4.6 mm ID x 15 cm) as columns, and THF (tetrahydrofuran) as an eluent.

[0016] In the present specification, each component may be used alone or in combination of two or more substances corresponding to the component. When two or more substances are used in combination for each component, the content of the component refers to the total content of the substances used in combination, unless otherwise specified.

[0017] [Magnetic particle-containing composition] The magnetic particle-containing composition of the present invention (hereinafter also simply referred to as "composition") contains magnetic particles having multiple peak tops in a particle size distribution curve that represents a volume-based frequency distribution, a resin, and a solvent. The magnetic particle-containing composition of the present invention is capable of forming a magnetic particle-containing film having excellent sedimentation stability and excellent magnetic permeability. Although the details of the reason for this are not clear, it is generally assumed to be as follows.

[0018] It is known that if the average particle size of the magnetic particles is not large enough, the magnetic permeability of the magnetic particle-containing film obtained by using the magnetic particles will be insufficient. However, the present inventors have found that the magnetic permeability cannot be sufficiently increased by simply using magnetic particles with a large average particle size, because the gaps between the magnetic particles become large. The present inventors have found that the magnetic permeability can be improved by using magnetic particles having multiple peak tops in a particle size distribution curve that represents a volume-based frequency distribution. The reason for this is presumably that the gaps between the magnetic particles in the magnetic particle-containing film are reduced by arranging magnetic particles with small average particle diameters between magnetic particles with large average particle diameters. On the other hand, there is a problem that magnetic particles having a large average particle size settle over time in the magnetic particle-containing composition. In response to this problem, it has been found that the sedimentation of magnetic particles can be suppressed by using a magnetic particle-containing composition that contains magnetic particles that have multiple peak tops in a particle size distribution curve that represents a volume-based frequency distribution, and a resin.The reason for this is presumably that the magnetic particles with small average particle diameters are aligned by the action of a magnetic field that exists between magnetic particles with large average particle diameters, and then the magnetic particles are loosely bound together by the action of the resin, improving the static viscosity of the magnetic particle-containing composition and suppressing the sedimentation of the magnetic particles.

[0019] [Magnetic particles] The composition contains magnetic particles having multiple peak tops in a particle size distribution curve that represents a volume-based frequency distribution. The material constituting the magnetic particles preferably contains a metal element, and more preferably contains at least one metal element selected from the group consisting of Fe, Ni and Co. The above metal elements may be contained in the magnetic particles as an alloy containing the metal element (preferably a magnetic alloy), a metal oxide (preferably a magnetic oxide), a metal nitride (preferably a magnetic oxide), or a metal carbide (preferably a magnetic carbide). The material constituting the magnetic particles may contain elements other than Fe, Ni, and Co, and specific examples include Al, Si, S, Sc, Ti, V, Cu, Y, Mo, Rh, Pd, Ag, Sn, Sb, Te, Ba, Ta, W, Re, Au, Bi, La, Ce, Pr, Nd, P, Zn, Sr, Zr, Mn, Cr, Nb, Pb, Ca, B, C, and N.

[0020] Specific examples of materials constituting the magnetic particles include Fe-Co based alloys (preferably permendur), Fe-Ni based alloys (e.g. permalloy), Fe-Zr based alloys, Fe-Mn based alloys, Fe-Si based alloys, Fe-Al based alloys, Ni-Mo based alloys (preferably supermalloy), Fe-Ni-Co based alloys, Fe-Si-Cr based alloys, Fe-Si-B based alloys, Fe-Si-Al based alloys (preferably sendust), Fe-Si-BC based alloys, Fe-Si-B- Examples of the alloy include Cr-based alloys, Fe-Si-B-Cr-C-based alloys, Fe-Co-Si-B-based alloys, Fe-Si-B-Nb-based alloys, Fe nanocrystalline alloys, Fe-based amorphous alloys, and Co-based amorphous alloys, as well as ferrites such as spinel ferrites (preferably Ni-Zn-based ferrites, Mn-Zn-based ferrites) and hexagonal ferrites (preferably barium ferrites, magnetoplumbite-type hexagonal ferrites represented by the formula (F1) described below). The alloys may be amorphous. Among these, alloys are preferred in terms of superior magnetic permeability of the magnetic particle-containing film, and Fe-based amorphous alloys, Fe-Si-Cr alloys, Fe nanocrystalline alloys, Fe-Ni-Co alloys, Co-based amorphous alloys, and Ni-Mo alloys are more preferred. Furthermore, in terms of superior chemical stability of the magnetic particle-containing film, ferrite is preferred, and spinel ferrite is more preferred. The materials constituting the magnetic particles may be used alone or in combination of two or more kinds.

[0021] Formula (F1) is as follows. AFe (12-X) Al X O 19 Formula (F1) In formula (F1), A represents at least one metal element selected from the group consisting of Sr, Ba, Ca, and Pb, and x satisfies 1.5≦x≦8.0.

[0022] As long as A in formula (F1) is at least one metal element selected from the group consisting of Sr, Ba, Ca, and Pb, the type and number of the metal element are not particularly limited. For example, from the viewpoint of operability and handling, A in formula (F1) is preferably at least one metal element selected from the group consisting of Sr, Ba, and Ca. In formula (F1), x satisfies 1.5≦x≦8.0, preferably satisfies 1.5≦x≦6.0, and more preferably satisfies 2.0≦x≦6.0. When x in formula (F1) is 1.5 or more, radio waves in a frequency band higher than 60 GHz can be absorbed. When x in formula (F1) is 8.0 or less, the magnetoplumbite-type hexagonal ferrite particles have magnetism.

[0023] A specific example of the magnetoplumbite-type hexagonal ferrite represented by formula (F1) is SrFe (9.58) Al (2.42) O 19 , SrFe (9.37) Al (2.63) O 19 , SrFe (9.27) Al (2.73) O 19 , SrFe (9.85) Al (2.15) O 19 , SrFe (10.00) Al (2.00) O 19 , SrFe (9.74) Al (2.26) O 19 , SrFe (10.44) Al (1.56) O 19 , SrFe (9.79) Al (2.21) O 19 , SrFe (9.33) Al (2.67) O 19 , SrFe (7.88) Al (4.12)O 19 , SrFe (7.04) Al (4.96) O 19 , SrFe (7.37) Al (4.63) O 19 , SrFe (6.25) Al (5.75) O 19 , SrFe (7.71) Al (4.29) O 19 , Sr (0.80) Ba (0.10) Ca (0.10) Fe (9.83) Al (2.17) O 19 , BaFe (9.50) Al (2.50) O 19 , Cafe (10.00) Al (2.00) O 19 , PbFe (9.00) Al (3.00) O 19 Examples include:

[0024] The composition of the magnetoplumbite-type hexagonal ferrite particles is confirmed by high-frequency inductively coupled plasma (ICP) emission spectrometry. Specifically, a pressure-resistant container containing 12 mg of sample particles and 10 mL of 4 mol / L (liter; the same applies below) hydrochloric acid solution is kept in an oven set at a temperature of 120°C for 12 hours to obtain a solution. Next, 30 mL of pure water is added to the obtained solution, and then it is filtered using a 0.1 μm membrane filter. The elemental analysis of the filtrate thus obtained is performed using an inductively coupled plasma (ICP) optical emission spectrometer. Based on the results of the elemental analysis obtained, the content of each metal atom relative to 100 atomic % of iron atoms is calculated. The composition is confirmed based on the obtained content. As a measuring device, for example, a high-frequency inductively coupled plasma (ICP) optical emission spectrometer (model: ICPS-8100) manufactured by Shimadzu Corporation can be suitably used, although the measuring device is not limited to this.

[0025] The magnetoplumbite hexagonal ferrite represented by formula (F1) is preferably a magnetoplumbite hexagonal ferrite having a single crystal phase. In this specification, the case where the "crystal phase is single phase" refers to a case where only one type of diffraction pattern showing the crystal structure of magnetoplumbite-type hexagonal ferrite of any composition is observed in powder X-ray diffraction (XRD: X-Ray-Diffraction) measurement. In other words, it refers to a case where a plurality of magnetoplumbite-type hexagonal ferrites of any composition are mixed, and two or more types of diffraction patterns are observed, or a diffraction pattern of a crystal other than magnetoplumbite-type hexagonal ferrite is not observed. For the attribution of the diffraction pattern, for example, the database of the International Centre for Diffraction Data (ICDD: International Centre for Diffraction Data, registered trademark) can be referred to. For example, the diffraction pattern of magnetoplumbite-type hexagonal ferrite containing Sr can be referred to "00-033-1340" of the International Centre for Diffraction Data (ICDD). However, the peak position shifts due to the substitution of a part of iron with aluminum.

[0026] Whether the magnetoplumbite-type hexagonal ferrite has a single crystal phase can be confirmed by, for example, an X-ray diffraction (XRD) method. Specifically, the measurement can be performed using a powder X-ray diffractometer under the following conditions. As a measuring device, for example, an X'Pert Pro diffractometer manufactured by PANalytical Inc. can be suitably used, although the measuring device is not limited thereto.

[0027] -conditions- X-ray source: CuKα ray [Wavelength: 1.54 Å (0.154 nm), Output: 40 mA, 45 kV] Scan range: 20°<2θ<70° Scan interval: 0.05° Scan speed: 0.75° / min

[0028] The magnetic particles may have a surface layer on the surface thereof, and by having the surface layer on the magnetic particles in this way, it is possible to impart a function to the magnetic particles according to the material of the surface layer. The surface layer may be an inorganic layer or an organic layer.

[0029] As the inorganic layer-forming compound, metal oxides, metal nitrides, metal carbides, metal phosphate compounds, metal borate compounds, or silicate compounds (e.g., silicate esters such as tetraethyl orthosilicate, and silicates such as sodium silicate) are preferred, since they can form a surface layer that is excellent in at least one of insulation, gas barrier properties, and chemical stability. Specific examples of elements contained in these compounds include Fe, Al, Ca, Mn, Zn, Mg, V, Cr, Y, Ba, Sr, Ge, Zr, Ti, Si, and rare earth elements. Materials constituting the inorganic layer obtained using the compound for forming an inorganic layer include silicon oxide, germanium oxide, titanium oxide, aluminum oxide, zirconium oxide, magnesium oxide, etc., and the inorganic layer may be a layer containing two or more of these.

[0030] Examples of the organic layer-forming compound include acrylic monomers. Specific examples of the acrylic monomer include the compounds described in paragraphs 0022 to 0023 of JP-A-2019-67960. Examples of materials constituting the organic layer obtained by using the organic layer-forming compound include acrylic resins.

[0031] The thickness of the surface layer is not particularly limited, but is preferably from 3 to 1000 nm in order to better exhibit the function of the surface layer.

[0032] The magnetic particles preferably contain a metal element with a standard oxidation-reduction potential of at least −0.3 V. This makes it possible to suppress dissolution of the magnetic particles by acid, thereby improving the chemical stability of the magnetic permeability of the magnetic particle-containing film. Specific examples of metal elements having a standard oxidation-reduction potential of -0.3 V or higher include Ni and Co. The lower limit of the standard oxidation-reduction potential of the metal element is preferably −0.3 V or more, particularly preferably −0.27 V or more. The upper limit of the standard oxidation-reduction potential of the metal element is preferably 1.5 V or less. The content of the metal element having a standard redox potential of -0.3 V or more is preferably 30 mass % or more, and more preferably 40 mass % or more, based on the total mass of the magnetic particles, in order to provide a magnetic particle-containing film with superior magnetic permeability. The upper limit of the content of the metal element having a standard redox potential of -0.3 V or more is preferably 100 mass % or less, and more preferably 95 mass % or less. In this specification, the standard oxidation-reduction potential values ​​are those described in the Chemical Handbook (5th edition).

[0033] The content of the magnetic particles is preferably 10 mass % or more, more preferably 25 mass % or more, even more preferably 40 mass % or more, particularly preferably 50 mass % or more, and most preferably 60 mass % or more, relative to the total mass of the composition, in order to obtain a magnetic particle-containing film with better magnetic permeability. The content of the magnetic particles is preferably 95% by mass or less, and more preferably 90% by mass or less, based on the total mass of the composition, in that the sedimentation stability of the magnetic particles is superior. The content of the magnetic particles is preferably 10 to 99 mass %, particularly preferably 40 to 97 mass %, based on the total solid content of the composition, in that the magnetic permeability of the magnetic particle-containing film is superior.

[0034] <Average primary particle diameter> The average primary particle size of the magnetic particles is preferably from 0.001 to 100 μm, more preferably from 0.01 to 50 μm, further preferably from 0.1 to 30 μm, and particularly preferably from 0.5 to 25 μm. It is preferable to use a combination of a plurality of magnetic particles having different average primary particle sizes, since this makes it easy to obtain magnetic particles having a plurality of peak tops in a particle size distribution curve that represents a volume-based frequency distribution.

[0035] The particle diameter of the primary particles of the magnetic particles is measured by photographing the magnetic particles with a transmission electron microscope at a magnification of 100,000 times, printing the photograph on photographic paper to a total magnification of 500,000 times, tracing the outline of the particle (primary particle) with a digitizer, and calculating the diameter of a circle with the same area as the traced area (circular area diameter). Here, primary particles refer to independent particles without aggregation. Photographing using a transmission electron microscope is performed by a direct method using a transmission electron microscope with an acceleration voltage of 300 kV. Observation and measurement using a transmission electron microscope can be performed, for example, using a Hitachi transmission electron microscope H-9000 model and Carl Zeiss image analysis software KS-400.

[0036] Regarding the shape of magnetic particles, "plate-like" refers to a shape having two opposing plate surfaces. On the other hand, among particle shapes that do not have such plate surfaces, a shape with a distinction between a long axis and a short axis is "elliptical". The long axis is determined as the axis (straight line) that can take the longest length of the particle. On the other hand, the short axis is determined as the axis that is the longest when the particle length is taken along a straight line perpendicular to the long axis. A shape in which there is no distinction between the long axis and the short axis, that is, a shape in which the long axis length = the short axis length, is "spherical". A shape in which the long axis and the short axis cannot be specified from the shape is called an indefinite shape. The above-mentioned photographing using a transmission electron microscope for identifying the particle shape is performed without applying an orientation treatment to the particles to be photographed. The shape of the magnetic particles may be any of plate-like, elliptical, spherical, and indefinite.

[0037] Here, when a commercially available product is used, the average primary particle size of each type of particle described in this specification is the catalog value. If no catalog value is available, the particle size shall be determined by taking the arithmetic average of the values ​​obtained for 500 particles randomly selected using the particle photograph taken as described above.

[0038] <Particle size distribution> The magnetic particles contained in the composition have multiple peak tops in a particle size distribution curve that represents a volume-based frequency distribution. In this specification, a particle size distribution curve that represents a volume-based frequency distribution is also referred to as a "frequency distribution curve." Fig. 1 is a particle size distribution diagram showing an example of a frequency distribution curve of the magnetic particles contained in the composition of the present invention. As shown in Fig. 1, the frequency distribution curve is expressed as a particle size distribution diagram with the horizontal axis representing particle diameter and the vertical axis representing frequency (%).

[0039] The frequency distribution curve in the present invention is obtained as follows. First, the composition is diluted with a main solvent as necessary, and ultrasonic dispersion is performed for 60 minutes to prepare a dispersion liquid. Note that the composition is not diluted when the content of magnetic particles in the composition is 5% by mass or less, and is diluted so that the content of magnetic particles in the diluted dispersion liquid becomes 5% by mass when the content of magnetic particles in the composition is more than 5% by mass. In addition, the main solvent means the solvent with the largest content among the solvents contained in the composition. Next, the dispersion is measured using a laser diffraction scattering type particle size distribution measuring device (product name "LA960N", manufactured by Horiba, Ltd.) in a measurement range mode of 0.01 μm to 5000 μm, and a particle size distribution curve showing the volume-based frequency distribution of the magnetic particles contained in the composition is obtained.

[0040] The peak top in a frequency distribution curve means a maximum point in the frequency distribution curve. In the example of FIG. 1, the frequency distribution curve has two peak tops, namely, a peak top Pmin having the smallest particle diameter and a peak top Pmax having the largest particle diameter, but the number of peak tops is not limited to this. The number of peak tops in the frequency distribution curve is multiple (ie, two or more), preferably 2 to 5, more preferably 2 to 4, even more preferably 2 to 3, and particularly preferably 2 in terms of magnetic permeability and film formability.

[0041] When the particle diameter at the peak top Pmin having the smallest particle diameter among multiple peak tops in a frequency distribution curve is defined as Dmin, and the particle diameter at the peak top Pmax having the largest particle diameter is defined as Dmax, the ratio of Dmax to Dmin (Dmax / Dmin) is preferably more than 2, more preferably 3 or more, and particularly preferably 4 or more, in terms of better effects of the present invention. The upper limit of the ratio (Dmax / Dmin) is preferably 150 or less, more preferably 100 or less, further preferably 50 or less, and particularly preferably 10 or less, in terms of obtaining better effects of the present invention. The ratio (Dmax / Dmin) can be adjusted to fall within the above range, for example, by using a plurality of magnetic particles having different primary particle sizes and appropriately adjusting the blending ratio thereof.

[0042] Fig. 2 is a particle size distribution diagram showing an example of a particle size distribution curve showing the cumulative distribution on a volume basis of the magnetic particles contained in the composition of the present invention. As shown in Fig. 2, the particle size distribution curve showing the cumulative distribution on a volume basis is shown in a particle size distribution diagram with the horizontal axis representing particle diameter and the vertical axis representing accumulation (%). In this specification, the particle size distribution curve showing the cumulative distribution on a volume basis is also referred to as a "cumulative distribution curve". The cumulative distribution curve is measured in the same manner as the particle size distribution curve, which represents a volume-based frequency distribution. Dmin is the particle diameter D at which the cumulative distribution curve reaches 80%, from the viewpoint of the effect of the present invention being more excellent. 80 It is preferable that the particle diameter D at 60% of the cumulative distribution curve is less than or equal to 60 It is particularly preferred that: Dmin is the particle diameter D at which the cumulative distribution curve reaches 10%, from the viewpoint of the effect of the present invention being more excellent. 10 It is preferable that the particle diameter D at the time when the cumulative distribution curve reaches 20% is equal to or larger than the particle diameter D at the time when the cumulative distribution curve reaches 20%. 20 More preferably, it is equal to or greater than this. In view of the superior effect of the present invention, Dmin is preferably from 0.1 to 50 μm, more preferably from 0.5 to 25 μm, and particularly preferably from 1 to 10 μm.

[0043] Dmax is the particle diameter D at which the cumulative distribution curve reaches 90% from the viewpoint of the effect of the present invention being more excellent. 90 It is preferable that the particle diameter D at 80% of the cumulative distribution curve is less than or equal to 80 It is particularly preferred that: Dmax is the particle diameter D at 20% of the cumulative distribution curve, which is the most advantageous effect of the present invention. 20 It is preferable that the particle diameter D at the time when the cumulative distribution curve reaches 40% is equal to or larger than the particle diameter D at the time when the cumulative distribution curve reaches 40%. 40 More preferably, it is equal to or greater than this. In terms of obtaining superior effects of the present invention, Dmax is preferably from 1 to 150 μm, more preferably from 1 to 100 μm, further preferably from 5 to 75 μm, and particularly preferably from 7.5 to 50 μm.

[0044] 〔resin〕 The composition contains a resin. Examples of the resin include (meth)acrylic resin, epoxy resin, enethiol resin, polycarbonate resin, polyether resin, polyarylate resin, polysulfone resin, polyethersulfone resin, polyphenylene resin, polyarylene ether phosphine oxide resin, polyimide resin, polyamideimide resin, polyolefin resin, cyclic olefin resin, polyester resin, styrene resin, and phenoxy resin. One of these resins may be used alone, or two or more may be mixed and used. As the cyclic olefin resin, norbornene resin is preferable from the viewpoint of improving heat resistance. Examples of commercially available norbornene resins include the ARTON series (e.g., ARTON F4520) manufactured by JSR Corporation. Examples of epoxy resins include epoxy resins which are glycidyl ethers of phenolic compounds, epoxy resins which are glycidyl ethers of various novolac resins, alicyclic epoxy resins, aliphatic epoxy resins, heterocyclic epoxy resins, glycidyl ester epoxy resins, glycidylamine epoxy resins, epoxy resins obtained by glycidylating halogenated phenols, condensates of silicon compounds having epoxy groups and other silicon compounds, copolymers of polymerizable unsaturated compounds having epoxy groups and other polymerizable unsaturated compounds, etc. Also, examples of epoxy resins that can be used include Marproof G-0150M, G-0105SA, G-0130SP, G-0250SP, G-1005S, G-1005SA, G-1010S, G-2050M, G-01100, and G-01758 (manufactured by NOF Corp., epoxy group-containing polymers). The resin may be any of those described in the examples of WO 2016 / 088645. When the resin has an ethylenically unsaturated group, particularly a (meth)acryloyl group, in a side chain, it is also preferred that the main chain and the ethylenically unsaturated group are bonded via a divalent linking group having an alicyclic structure.

[0045] One preferred embodiment of the resin is a resin having a polymerizable group such as an unsaturated double bond (e.g., an ethylenically unsaturated double bond), an epoxy group, or an oxetanyl group. When the polymerizable group reacts during the formation of the magnetic particle-containing film, a magnetic particle-containing film having excellent mechanical strength is obtained. Examples of such resins include polymers having epoxy groups in their side chains, and polymerizable monomers or oligomers having two or more epoxy groups in their molecules. Specific examples of such resins include bisphenol A type epoxy resins, bisphenol F type epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins, and aliphatic epoxy resins. These resins may be commercially available products, or may be obtained by introducing an epoxy group into the side chain of a polymer. For commercially available products, see, for example, paragraph 0191 of JP 2012-155288 A, the contents of which are incorporated herein by reference. Other examples include ADEKA RESIN EP-4000S, EP-4003S, EP-4010S, and EP-4011S (all manufactured by ADEKA Corporation), NC-2000, NC-3000, NC-7300, XD-1000, EPPN-501, and EPPN-502 (all manufactured by ADEKA Corporation), and JER1031S. Furthermore, commercially available products of phenol novolac type epoxy resins include JER-157S65, JER-152, JER-154, and JER-157S70 (all manufactured by Mitsubishi Chemical Corporation). Specific examples of polymers having oxetanyl groups in their side chains and polymerizable monomers or oligomers having two or more oxetanyl groups in the molecule include Aron Oxetane OXT-121, OXT-221, OX-SQ, and PNOX (all manufactured by Toagosei Co., Ltd.). When an epoxy group is introduced into a polymer side chain to synthesize a resin having an epoxy group, the introduction reaction can be carried out by reacting for a predetermined time at a reaction temperature of 50 to 150°C in an organic solvent using, for example, a tertiary amine such as triethylamine or benzylmethylamine, a quaternary ammonium salt such as dodecyltrimethylammonium chloride, tetramethylammonium chloride, or tetraethylammonium chloride, pyridine, or triphenylphosphine as a catalyst. The amount of the alicyclic epoxy unsaturated compound introduced can be controlled so that the acid value of the resulting polymer is in the range of 5 to 200 KOH mg / g. The weight average molecular weight can be set to a range of 500 to 5,000,000, preferably 1,000 to 500,000. Instead of the alicyclic epoxy unsaturated compound, compounds having a glycidyl group as an epoxy group such as glycidyl (meth)acrylate and allyl glycidyl ether can also be used. For such compounds, see, for example, paragraph 0045 of JP-A-2009-265518, the contents of which are incorporated herein by reference.

[0046] One of the preferred embodiments of the resin is a resin having an acid group, a basic group, or an amide group. A resin having an acid group, a basic group, or an amide group is preferred because it easily functions as a dispersant for dispersing magnetic particles and provides a superior effect of the present invention. Examples of the acid group include a carboxy group, a phosphate group, a sulfo group, and a phenolic hydroxyl group. The carboxy group is preferred in terms of obtaining superior effects of the present invention. Examples of the basic group include an amino group (a group in which one hydrogen atom has been removed from ammonia, a primary amine, or a secondary amine) and an imino group. In particular, the resin preferably has a carboxy group or an amide group, since the effects of the present invention are more excellent.

[0047] When the resin has an acid group, the acid value of the resin is preferably from 10 to 500 mgKOH / g, particularly preferably from 30 to 400 mgKOH / g, in terms of better effects of the present invention.

[0048] As the resin, it is preferable to use a resin having a solubility in the solvent of 10 g / L or more, and it is more preferable to use a resin having a solubility in the solvent of 20 g / L or more, since this improves the dispersibility of the resin in the composition and the effects of the present invention are more excellent. The upper limit of the solubility of the resin in the solvent is preferably 2000 g / L or less, particularly preferably 1000 g / L or less. The solubility of a resin in a solvent means the amount (g) of the resin that can be dissolved in 1 L of the solvent at 25°C.

[0049] The resin content is preferably 0.1 to 30 mass%, more preferably 1 to 20 mass%, further preferably 2 to 15 mass%, and particularly preferably 2.5 to 10 mass%, relative to the total mass of the composition, in terms of better effects of the present invention.

[0050] <Resin that functions as a dispersant> One of the preferred embodiments of the resin is a resin that functions as a dispersant for dispersing magnetic particles in the composition (hereinafter, also referred to as a "dispersion resin"). By using a dispersion resin, the effects of the present invention are more excellent. Preferred embodiments of the dispersing resin include a resin having a repeating unit containing a graft chain, an aggregation control agent, and an aggregation dispersant, which will be described later.

[0051] (Resin having a repeating unit containing a graft chain) The dispersing resin may be a resin having a repeating unit containing a graft chain (hereinafter, also referred to as "resin A"). However, resin A may also be used for purposes other than functioning as a dispersing agent.

[0052] When the composition contains resin A, the content of resin A is preferably 0.1 to 30 mass%, more preferably 0.5 to 20 mass%, and particularly preferably 1 to 10 mass%, relative to the total mass of the composition, in terms of better effects of the present invention.

[0053] Repeating units containing graft chains In a repeating unit containing a graft chain, as the graft chain becomes longer, the steric repulsion effect increases, and the dispersibility of the magnetic particles improves. On the other hand, if the graft chain is too long, the adsorptive force to the magnetic particles decreases, and the dispersibility of the magnetic particles tends to decrease. For this reason, the graft chain preferably has an atomic number excluding hydrogen atoms of 40 to 10,000, more preferably an atomic number excluding hydrogen atoms of 50 to 2,000, and even more preferably an atomic number excluding hydrogen atoms of 60 to 500. Here, the graft chain refers to a chain extending from the root of the main chain (an atom attached to the main chain in a group branching from the main chain) to the end of the group branching from the main chain.

[0054] Furthermore, the graft chain preferably contains a polymer structure. Examples of such polymer structures include a poly(meth)acrylate structure (e.g., a poly(meth)acrylic structure), a polyester structure, a polyurethane structure, a polyurea structure, a polyamide structure, and a polyether structure. In order to improve the interaction between the graft chain and the solvent and thereby enhance the dispersibility of the magnetic particles, the graft chain is preferably a graft chain containing at least one structure selected from the group consisting of a polyester structure, a polyether structure, and a poly(meth)acrylate structure, and more preferably a graft chain containing at least one of a polyester structure and a polyether structure.

[0055] Resin A may be a resin obtained by using a macromonomer containing a graft chain (a monomer having a polymer structure and bonding to a main chain to form a graft chain). The macromonomer containing a graft chain (a monomer having a polymer structure and bonding to a main chain to form a graft chain) is not particularly limited, but a macromonomer containing a reactive double bond group can be preferably used.

[0056] As commercially available macromonomers corresponding to the repeating units containing the graft chain and suitable for use in the synthesis of resin A, AA-6, AA-10, AB-6, AS-6, AN-6, AW-6, AA-714, AY-707, AY-714, AK-5, AK-30, and AK-32 (all trade names, manufactured by Toagosei Co., Ltd.), as well as Blenmer PP-100, Blenmer PP-500, Blenmer PP-800, Blenmer PP-1000, Blenmer 55-PET-800, Blenmer PME-4000, Blenmer PSE-400, Blenmer PSE-1300, and Blenmer 43PAPE-600B (all trade names, manufactured by NOF Corp.) are used. Among these, AA-6, AA-10, AB-6, AS-6, AN-6, or Blenmer PME-4000 are preferred.

[0057] Resin A preferably contains at least one structure selected from the group consisting of polymethyl acrylate, polymethyl methacrylate, and cyclic or linear polyester, more preferably contains at least one structure selected from the group consisting of polymethyl acrylate, polymethyl methacrylate, and linear polyester, and particularly preferably contains at least one structure selected from the group consisting of polymethyl acrylate structure, polymethyl methacrylate structure, polycaprolactone structure, and polyvalerolactone structure. Resin A may contain one of the above structures alone, or may contain a plurality of these structures. Here, the polycaprolactone structure refers to a structure containing a ring-opened ε-caprolactone structure as a repeating unit, and the polyvalerolactone structure refers to a structure containing a ring-opened δ-valerolactone structure as a repeating unit.

[0058] When resin A contains repeating units in which j and k are 5 in formula (1) described below and formula (2) described below, the above-mentioned polycaprolactone structure can be introduced into resin A. Furthermore, when resin A contains repeating units in which j and k are 4 in formula (1) described below and formula (2) described below, the above-mentioned polyvalerolactone structure can be introduced into the resin. In addition, the resin A is X in the formula (4) described below. 5 is a hydrogen atom, and R 4 When the resin A contains a repeating unit in which is a methyl group, the above-mentioned polymethyl acrylate structure can be introduced into the resin A. In addition, the resin A is X in the formula (4) described below. 5 is a methyl group, and R 4 When the resin A contains a repeating unit in which is a methyl group, the above-mentioned polymethyl methacrylate structure can be introduced into the resin A.

[0059] Resin A preferably contains, as a repeating unit including a graft chain, a repeating unit represented by any one of the following formulae (1) to (4), and more preferably contains a repeating unit represented by any one of the following formulae (1A), (2A), (3A), (3B), and (4).

[0060] [ka]

[0061] In formulas (1) to (4), W 1 , W 2 , W 3 , and W 4 Each independently represents an oxygen atom or NH. 1 , W 2 , W 3 , and W 4 is preferably an oxygen atom. In formulas (1) to (4), X 1 , X 2 , X 3 , X 4 , and X 5 Each of X independently represents a hydrogen atom or a monovalent organic group. 1 , X 2 , X 3 , X 4 , and X 5 From the viewpoint of synthetic constraints, each of the groups is preferably a hydrogen atom or an alkyl group having 1 to 12 carbon atoms (number of carbon atoms), more preferably a hydrogen atom or a methyl group, and even more preferably a methyl group.

[0062] In formulas (1) to (4), Y 1 , Y 2 , Y 3 , and Y 4 Each of Y independently represents a divalent linking group, and the linking group is not particularly limited in structure. 1 , Y 2 , Y 3 , and Y 4 Specific examples of the divalent linking group represented by the formula include the following linking groups (Y-1) to (Y-21). In the structures shown below, A and B respectively represent the bonding sites with the left and right terminal groups in formulas (1) to (4). Among the structures shown below, (Y-2) or (Y-13) is more preferred from the viewpoint of ease of synthesis.

[0063] [ka]

[0064] In formulas (1) to (4), Z 1 , Z 2 , Z 3 , and Z 4 Each of Z independently represents a monovalent organic group. The structure of the organic group is not particularly limited, but specific examples include an alkyl group, a hydroxyl group, an alkoxy group, an aryloxy group, a heteroaryloxy group, an alkylthioether group, an arylthioether group, a heteroarylthioether group, and an amino group. Among these, Z 1 , Z 2 , Z 3 , and Z 4 As the organic group represented by the formula (I), a group having a steric repulsion effect is preferable, particularly from the viewpoint of improving dispersibility, and each independently an alkyl group or alkoxy group having 5 to 24 carbon atoms is more preferable, and among these, each independently a branched alkyl group having 5 to 24 carbon atoms, a cyclic alkyl group having 5 to 24 carbon atoms, or an alkoxy group having 5 to 24 carbon atoms is even more preferable. The alkyl group contained in the alkoxy group may be any of linear, branched, and cyclic.

[0065] In the formulas (1) to (4), n, m, p, and q each independently represent an integer of 1 to 500. In the formulae (1) and (2), j and k each independently represent an integer of 2 to 8. In the formulae (1) and (2), j and k each preferably represent an integer of 4 to 6, and more preferably 5. In addition, in formulas (1) and (2), n and m are preferably integers of 10 or more, and more preferably integers of 20 or more. In addition, when resin A contains a polycaprolactone structure and a polyvalerolactone structure, the sum of the repeating number of the polycaprolactone structure and the repeating number of the polyvalerolactone structure is preferably an integer of 10 or more, and more preferably an integer of 20 or more.

[0066] In formula (3), R 3 represents a branched or linear alkylene group, preferably an alkylene group having 1 to 10 carbon atoms, more preferably an alkylene group having 2 or 3 carbon atoms. 3 may be the same or different from each other. In formula (4), R 4 R represents a hydrogen atom or a monovalent organic group, and the structure of this monovalent organic group is not particularly limited. 4 R is preferably a hydrogen atom, an alkyl group, an aryl group, or a heteroaryl group, and more preferably a hydrogen atom or an alkyl group. 4 When is an alkyl group, the alkyl group is preferably a linear alkyl group having 1 to 20 carbon atoms, a branched alkyl group having 3 to 20 carbon atoms, or a cyclic alkyl group having 5 to 20 carbon atoms, more preferably a linear alkyl group having 1 to 20 carbon atoms, and further preferably a linear alkyl group having 1 to 6 carbon atoms. In formula (4), when q is 2 to 500, a plurality of X present in the graft chain 5 and R 4 may be the same or different from each other.

[0067] Resin A may contain repeating units having two or more different structures, including a graft chain. That is, the molecule of resin A may contain repeating units represented by formulas (1) to (4) having structures different from one another, and when n, m, p, and q in formulas (1) to (4) each represent an integer of 2 or more, in formulas (1) and (2), j and k may have structures different from one another in the side chain, and in formulas (3) and (4), R present in a plurality of units in the molecule may be 0.01 to 0.01. 3 , R 4 , and X 5 may be the same or different from each other.

[0068] The repeating unit represented by formula (1) is more preferably a repeating unit represented by the following formula (1A). The repeating unit represented by formula (2) is more preferably a repeating unit represented by the following formula (2A).

[0069] [ka]

[0070] In formula (1A), X 1 , Y 1 , Z 1 , and n is X in formula (1). 1 , Y 1 , Z 1 In formula (2A), X has the same meaning as n, and the preferred range is also the same. 2 , Y 2 , Z 2 , and m is X in formula (2). 2 , Y 2 , Z 2 , and m, and the preferred ranges thereof are also the same.

[0071] The repeating unit represented by formula (3) is more preferably a repeating unit represented by the following formula (3A) or (3B).

[0072] [ka]

[0073] In formula (3A) or (3B), X 3 , Y 3 , Z 3 , and p is X in formula (3). 3 , Y 3 , Z 3 , and p have the same meanings and preferred ranges.

[0074] Resin A more preferably contains a repeating unit represented by formula (1A) as a repeating unit including a graft chain.

[0075] Resin A also preferably contains a repeating unit containing a polyalkyleneimine structure and a polyester structure. The repeating unit containing a polyalkyleneimine structure and a polyester structure preferably contains a polyalkyleneimine structure in the main chain and a polyester structure as a graft chain.

[0076] The polyalkyleneimine structure is a polymerized structure containing two or more identical or different alkyleneimine chains. Specific examples of the alkyleneimine chain include those represented by the following formula (4A) and formula (4B).

[0077] [ka]

[0078] In formula (4A), R X1 and R X2 each independently represents a hydrogen atom or an alkyl group. 1 represents an integer greater than or equal to 2. 1 represents a bonding position to a polyester chain, an adjacent alkyleneimine chain, or a hydrogen atom or a substituent.

[0079] [ka]

[0080] In formula (4B), R X3 and R X4 each independently represents a hydrogen atom or an alkyl group. 2 represents an integer of 2 or more. The alkyleneimine chain represented by formula (4B) is a polyester chain having an anionic group and a N + The anionic groups contained in the polyester chain form salt bridges, resulting in bonding.

[0081] * in formula (4A) and formula (4B), and * in formula (4B) 2 each independently represents a position at which the group is bonded to an adjacent alkyleneimine chain, or a hydrogen atom or a substituent. In particular, the * in the formula (4A) and the formula (4B) preferably represents the position at which the alkyleneimine chain is bonded to the adjacent alkyleneimine chain.

[0082] R in formula (4A) X1 and R X2 and R in formula (4B) X3 and R X4 each independently represents a hydrogen atom or an alkyl group. The alkyl group preferably has 1 to 6 carbon atoms, and more preferably has 1 to 3 carbon atoms. In formula (4A), R X1 and R X2 are preferably all hydrogen atoms. In formula (4B), R X3 and R X4 are preferably all hydrogen atoms.

[0083] a in formula (4A) 1 and a in formula (4B) 2 is not particularly limited as long as it is an integer of 2 or more. The upper limit is preferably 10 or less, more preferably 6 or less, even more preferably 4 or less, still more preferably 2 or 3, and particularly preferably 2.

[0084] In formula (4A) and formula (4B), * represents the bonding position to the adjacent alkyleneimine chain, or to a hydrogen atom or a substituent. Examples of the substituent include an alkyl group (for example, an alkyl group having 1 to 6 carbon atoms), etc. Furthermore, a polyester chain may be bonded as the substituent.

[0085] The alkyleneimine chain represented by formula (4A) is the same as that described above. 1 Specifically, it is preferable that the carbonyl carbon in the polyester chain is linked to the polyester chain at the position of 1 It is preferred that the bond is at the position The polyester chain may be represented by the following formula (5A).

[0086] [ka]

[0087] When the alkyleneimine chain is an alkyleneimine chain represented by formula (4B), the polyester chain is anionic (preferably an oxygen anion O - ), and the anionic group and the N in formula (4B) + It is preferred that these form a salt bridge. An example of such a polyester chain is a polyester chain represented by the following formula (5B).

[0088] [ka]

[0089] L in formula (5A) X1 and L in formula (5B) X2 each independently represents a divalent linking group. The divalent linking group is preferably an alkylene group having 3 to 30 carbon atoms.

[0090] b in formula (5A) 11 and b in formula (5B) 21each independently represents an integer of 2 or more, the upper limit of which is, for example, 200 or less.

[0091] b in formula (5A) 12 and b in formula (5B) 22 each independently represents 0 or 1.

[0092] X in formula (5A) A and X in formula (5B) B each independently represents a hydrogen atom or a substituent. Examples of the substituent include an alkyl group, an alkoxy group, a polyalkyleneoxyalkyl group, and an aryl group.

[0093] The number of carbon atoms in the alkyl group (which may be any of linear, branched, and cyclic) and the alkyl group contained in the alkoxy group (which may be any of linear, branched, and cyclic) can be 1 to 30, and preferably 1 to 10. The alkyl group may further have a substituent, and examples of the substituent include a hydroxyl group and a halogen atom (examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom).

[0094] Polyalkyleneoxyalkyl groups are R X6 (OR X7 ) p (O) q R is a substituent represented by the formula: X6 represents an alkyl group, R X7 represents an alkylene group, p represents an integer of 2 or more, and q represents 0 or 1. R X6 The alkyl group represented by X A In addition, R X7 The alkylene group represented by the formula: X A Examples of the alkyl group include those obtained by removing one hydrogen atom from the alkyl group represented by the following formula: p is an integer of 2 or more, and its upper limit is, for example, 10 or less, and preferably 5 or less.

[0095] The aryl group may be, for example, an aryl group having 6 to 24 carbon atoms (which may be either monocyclic or polycyclic). The aryl group may further have a substituent, and examples of the substituent include an alkyl group, a halogen atom, and a cyano group.

[0096] The polyester chain is preferably a structure obtained by ring-opening a lactone such as ε-caprolactone, δ-caprolactone, β-propiolactone, γ-butyrolactone, δ-valerolactone, γ-valerolactone, enantholactone, β-butyrolactone, γ-hexanolactone, γ-octanolactone, δ-hexalanolactone, δ-octanolactone, δ-dodecanolactone, α-methyl-γ-butyrolactone, or lactide (which may be either L- or D-form), and more preferably a structure obtained by ring-opening ε-caprolactone or δ-valerolactone.

[0097] The repeating unit containing the polyalkyleneimine structure and the polyester structure can be synthesized according to the synthesis method described in Japanese Patent No. 5,923,557.

[0098] In the resin A, the content of the repeating unit containing a graft chain is, in mass conversion, preferably 2 to 95 mass%, more preferably 2 to 90 mass%, and particularly preferably 5 to 30 mass%, based on the total mass of the resin A. When the repeating unit containing a graft chain is contained within this range, the effects of the present invention are more excellent.

[0099] Hydrophobic repeating units Resin A may also contain a hydrophobic repeating unit different from the repeating unit containing a graft chain (i.e., not corresponding to the repeating unit containing a graft chain). However, in this specification, a hydrophobic repeating unit is a repeating unit that does not have an acid group (e.g., a carboxylic acid group, a sulfonic acid group, a phosphoric acid group, a phenolic hydroxyl group, etc.).

[0100] The hydrophobic repeating unit is preferably a repeating unit derived from (corresponding to) a compound (monomer) having a ClogP value of 1.2 or more, and more preferably a repeating unit derived from a compound having a ClogP value of 1.2 to 8. This makes it possible to more reliably exhibit the effects of the present invention.

[0101] The ClogP value is a value calculated by the program "CLOGP" available from Daylight Chemical Information System, Inc. This program provides a "calculated logP" value calculated by the fragment approach of Hansch and Leo (see the literature below). The fragment approach is based on the chemical structure of a compound, and divides the chemical structure into partial structures (fragments), and estimates the logP value of the compound by summing up the logP contributions assigned to the fragments. Details are described in the literature below. In this specification, the ClogP value calculated by the program CLOGP v4.82 is used. AJ Leo, Comprehensive Medicinal Chemistry, Vol.4, C. Hansch, PG Sammnens, JB Taylor and CA Ramsden, Eds., p.295, Pergamon Press, 1990 C. Hansch & AJ Leo. SUbstituent Constants For Correlation Analysis in Chemistry and Biology. John Wiley & Sons. AJ Leo. Calculating logPoct from structure. Chem. Rev., 93, 1281-1306, 1993.

[0102] logP stands for the common logarithm of the partition coefficient P, and is a physical property that quantitatively represents how an organic compound is distributed in equilibrium in a two-phase system of oil (generally 1-octanol) and water, and is expressed by the following formula. logP = log(Coil / Cwater) In the formula, Coil represents the molar concentration of the compound in the oil phase, and Cwater represents the molar concentration of the compound in the water phase. As the logP value increases toward the positive side, around 0, the oil solubility increases, and as the absolute value increases toward the negative side, the water solubility increases. It has a negative correlation with the water solubility of organic compounds, and is widely used as a parameter to estimate the hydrophilicity or hydrophobicity of organic compounds.

[0103] Resin A preferably contains, as a hydrophobic repeating unit, one or more repeating units selected from repeating units derived from monomers represented by the following formulas (i) to (iii).

[0104] [ka]

[0105] In the above formulas (i) to (iii), R 1 , R 2 , and R 3 each independently represents a hydrogen atom, a halogen atom (for example, a fluorine atom, a chlorine atom, a bromine atom, etc.), or an alkyl group having 1 to 6 carbon atoms (for example, a methyl group, an ethyl group, a propyl group, etc.). R 1 , R 2 , and R 3 R is preferably a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, and more preferably a hydrogen atom or a methyl group. 2 and R 3 is more preferably a hydrogen atom. X represents an oxygen atom (-O-) or an imino group (-NH-), and is preferably an oxygen atom.

[0106] L is a single bond or a divalent linking group. Examples of the divalent linking group include a divalent aliphatic group (e.g., an alkylene group, a substituted alkylene group, an alkenylene group, a substituted alkenylene group, an alkynylene group, and a substituted alkynylene group), a divalent aromatic group (e.g., an arylene group, and a substituted arylene group), a divalent heterocyclic group, an oxygen atom (-O-), a sulfur atom (-S-), an imino group (-NH-), and a substituted imino group (-NR 31 -, where R 31 is an aliphatic group, an aromatic group, or a heterocyclic group), a carbonyl group (-CO-), and combinations thereof.

[0107] The divalent aliphatic group may have a cyclic structure or a branched structure. The number of carbon atoms in the aliphatic group is preferably 1 to 20, more preferably 1 to 15, and even more preferably 1 to 10. The aliphatic group may be an unsaturated aliphatic group or a saturated aliphatic group, but a saturated aliphatic group is preferred. The aliphatic group may have a substituent. Examples of the substituent include a halogen atom, an aromatic group, and a heterocyclic group.

[0108] The number of carbon atoms in the divalent aromatic group is preferably 6 to 20, more preferably 6 to 15, and further preferably 6 to 10. The aromatic group may have a substituent. Examples of the substituent include a halogen atom, an aliphatic group, an aromatic group, and a heterocyclic group.

[0109] The divalent heterocyclic group preferably contains a 5-membered or 6-membered ring as a heterocycle. The heterocycle may be condensed with another heterocycle, an aliphatic ring, or an aromatic ring. The heterocyclic group may have a substituent. Examples of the substituent include a halogen atom, a hydroxyl group, an oxo group (=O), a thioxo group (=S), an imino group (=NH), a substituted imino group (=NR 32 , where R 32 is an aliphatic group, an aromatic group, or a heterocyclic group), an aliphatic group, an aromatic group, and a heterocyclic group.

[0110] L is preferably a single bond, an alkylene group, or a divalent linking group containing an oxyalkylene structure. The oxyalkylene structure is more preferably an oxyethylene structure or an oxypropylene structure. L may also contain a polyoxyalkylene structure containing two or more repeating oxyalkylene structures. The polyoxyalkylene structure is preferably a polyoxyethylene structure or a polyoxypropylene structure. The polyoxyethylene structure is preferably a -(OCH 2 CH 2 )n-, where n is preferably an integer of 2 or more, and more preferably an integer of 2 to 10.

[0111] Z includes an aliphatic group (e.g., an alkyl group, a substituted alkyl group, an unsaturated alkyl group, a substituted unsaturated alkyl group), an aromatic group (e.g., an aryl group, a substituted aryl group, an arylene group, a substituted arylene group), a heterocyclic group, and combinations thereof. These groups include an oxygen atom (-O-), a sulfur atom (-S-), an imino group (-NH-), a substituted imino group (-NR 31 -, where R 31 may contain an aliphatic group, an aromatic group, or a heterocyclic group), or a carbonyl group (-CO-).

[0112] The aliphatic group may have a cyclic structure or a branched structure. The number of carbon atoms in the aliphatic group is preferably 1 to 20, more preferably 1 to 15, and even more preferably 1 to 10. The aliphatic group further includes a ring assembly hydrocarbon group and a bridged cyclic hydrocarbon group. Examples of the ring assembly hydrocarbon group include a bicyclohexyl group, a perhydronaphthalenyl group, a biphenyl group, and a 4-cyclohexylphenyl group. Examples of the bridged cyclic hydrocarbon ring include bicyclic hydrocarbon rings such as pinane, bornane, norpinane, norbornane, and bicyclooctane rings (such as bicyclo[2.2.2]octane ring and bicyclo[3.2.1]octane ring), homobredane, adamantane, and tricyclo[5.2.1.0]octane ring. 2,6 ]decane, and tricyclo[4.3.1.1 2,5 ]undecane ring and other tricyclic hydrocarbon rings, as well as tetracyclo[4.4.0.1 2,5 .1 7,10]dodecane, and tetracyclic hydrocarbon rings such as perhydro-1,4-methano-5,8-methanonaphthalene ring. The bridged cyclic hydrocarbon ring also includes condensed rings in which multiple 5- to 8-membered cycloalkane rings are condensed, such as perhydronaphthalene (decalin), perhydroanthracene, perhydrophenanthrene, perhydroacenaphthene, perhydrofluorene, perhydroindene, and perhydrophenalene rings. The aliphatic group is preferably a saturated aliphatic group rather than an unsaturated aliphatic group. The aliphatic group may have a substituent. Examples of the substituent include a halogen atom, an aromatic group, and a heterocyclic group. However, the aliphatic group does not have an acid group as a substituent.

[0113] The number of carbon atoms in the aromatic group is preferably 6 to 20, more preferably 6 to 15, and further preferably 6 to 10. The aromatic group may have a substituent. Examples of the substituent include a halogen atom, an aliphatic group, an aromatic group, and a heterocyclic group. However, the aromatic group does not have an acid group as a substituent.

[0114] The heterocyclic group preferably contains a 5- or 6-membered ring as a heterocycle. The heterocycle may be condensed with another heterocycle, an aliphatic ring, or an aromatic ring. The heterocyclic group may have a substituent. Examples of the substituent include a halogen atom, a hydroxyl group, an oxo group (=O), a thioxo group (=S), an imino group (=NH), a substituted imino group (=NR 32 , where R 32 is an aliphatic group, an aromatic group, or a heterocyclic group), an aliphatic group, an aromatic group, and a heterocyclic group, provided that the heterocyclic group does not have an acid group as a substituent.

[0115] In the above formula (iii), R 4 , R 5 , and R 6 R each independently represents a hydrogen atom, a halogen atom (e.g., a fluorine atom, a chlorine atom, a bromine atom, etc.), an alkyl group having 1 to 6 carbon atoms (e.g., a methyl group, an ethyl group, a propyl group, etc.), Z, or LZ, where L and Z are the same as the groups defined above. 4 , R5 , and R 6 is preferably a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, and more preferably a hydrogen atom.

[0116] As the monomer represented by the above formula (i), R 1 , R 2 , and R 3 is a hydrogen atom or a methyl group, L is a single bond or a divalent linking group containing an alkylene group or an oxyalkylene structure, X is an oxygen atom or an imino group, and Z is an aliphatic group, a heterocyclic group, or an aromatic group. In addition, as the monomer represented by the above formula (ii), R 1 is a hydrogen atom or a methyl group, L is an alkylene group, and Z is an aliphatic group, a heterocyclic group, or an aromatic group. 4 , R 5 , and R 6 Preferred are compounds in which is a hydrogen atom or a methyl group, and Z is an aliphatic group, a heterocyclic group, or an aromatic group.

[0117] Representative examples of the compounds represented by formulas (i) to (iii) include radically polymerizable compounds selected from acrylic acid esters, methacrylic acid esters, styrenes, and the like. Representative examples of the compounds represented by formulas (i) to (iii) can be found in the compounds described in paragraphs 0089 to 0093 of JP-A No. 2013-249417, the contents of which are incorporated herein by reference.

[0118] In the resin A, the content of the hydrophobic repeating unit is preferably from 10 to 90 mass %, and more preferably from 20 to 80 mass %, based on the total mass of the resin A, in terms of mass.

[0119] Functional groups that can interact with magnetic particles Resin A may have a functional group capable of forming an interaction with the magnetic particles. It is preferable that resin A further contains a repeating unit containing a functional group capable of forming an interaction with the magnetic particles. Examples of functional groups capable of forming interactions with magnetic particles include acid groups, basic groups, coordinating groups, and reactive functional groups. When Resin A contains an acid group, a basic group, a coordinating group, or a reactive functional group, it preferably contains a repeating unit containing an acid group, a repeating unit containing a basic group, a repeating unit containing a coordinating group, or a repeating unit having a reactive functional group, respectively.

[0120] The repeating unit containing an alkali-soluble group as an acid group may be the same as or different from the repeating unit containing the graft chain described above, but the repeating unit containing an alkali-soluble group as an acid group is a repeating unit different from the hydrophobic repeating unit described above (i.e., it does not correspond to the hydrophobic repeating unit described above).

[0121] Examples of the acid group, which is a functional group capable of forming an interaction with the magnetic particles, include a carboxylic acid group, a sulfonic acid group, a phosphoric acid group, and a phenolic hydroxyl group, and at least one of the carboxylic acid group, the sulfonic acid group, and the phosphoric acid group is preferred, and the carboxylic acid group is more preferred. The carboxylic acid group has a good adsorption force to the magnetic particles and high dispersibility. That is, it is preferable that resin A further contains a repeating unit containing at least one of a carboxylic acid group, a sulfonic acid group, and a phosphoric acid group.

[0122] Resin A may have one or more types of repeating units containing an acid group. When the resin A contains a repeating unit containing an acid group, the content thereof is preferably from 5 to 80 mass %, and more preferably from 10 to 60 mass %, based on the total mass of the resin A, in mass terms.

[0123] Examples of basic groups that are functional groups capable of forming interactions with magnetic particles include primary amino groups, secondary amino groups, tertiary amino groups, heterocycles containing N atoms, and amide groups, and a preferred basic group is a tertiary amino group because of its good adsorption to magnetic particles and high dispersibility. Resin A may contain one or more of these basic groups. When the resin A contains a repeating unit containing a basic group, the content thereof is preferably from 0.01 to 50 mass %, and more preferably from 0.01 to 30 mass %, based on the total mass of the resin A, in mass conversion.

[0124] Examples of functional groups that can form an interaction with magnetic particles, such as a coordinating group, and a reactive functional group, include an acetylacetoxy group, a trialkoxysilyl group, an isocyanate group, an acid anhydride, and an acid chloride. A preferred functional group is an acetylacetoxy group, which has good adsorption power to magnetic particles and high dispersibility of magnetic particles. Resin A may have one or more of these groups. When resin A contains a repeating unit containing a coordinating group or a repeating unit containing a reactive functional group, the content thereof is preferably 10 to 80 mass %, more preferably 20 to 60 mass %, based on the total mass of resin A, in mass terms.

[0125] When the resin A contains functional groups capable of forming interactions with magnetic particles other than the graft chains, it is sufficient that the resin A contains functional groups capable of forming interactions with the various magnetic particles, and there are no particular limitations on how these functional groups are introduced. For example, it is preferable that the resin contained in the composition contains one or more repeating units selected from repeating units derived from monomers represented by the following formulas (iv) to (vi).

[0126] [ka]

[0127] In formulas (iv) to (vi), R 11 , R 12 , and R 13each independently represents a hydrogen atom, a halogen atom (for example, a fluorine atom, a chlorine atom, a bromine atom, etc.), or an alkyl group having 1 to 6 carbon atoms (for example, a methyl group, an ethyl group, a propyl group, etc.). In formulas (iv) to (vi), R 11 , R 12 , and R 13 is preferably a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, and more preferably a hydrogen atom or a methyl group. 12 and R 13 is more preferably a hydrogen atom.

[0128] X in formula (iv) 1 represents an oxygen atom (-O-) or an imino group (-NH-), and is preferably an oxygen atom. In addition, Y in the formula (v) represents a methine group or a nitrogen atom.

[0129] In addition, L in formulas (iv) to (v) 1 represents a single bond or a divalent linking group. The definition of the divalent linking group is the same as the definition of the divalent linking group represented by L in formula (i) above.

[0130] L 1 is preferably a single bond, an alkylene group, or a divalent linking group containing an oxyalkylene structure. The oxyalkylene structure is more preferably an oxyethylene structure or an oxypropylene structure. 1 may contain a polyoxyalkylene structure containing two or more repeated oxyalkylene structures. The polyoxyalkylene structure is preferably a polyoxyethylene structure or a polyoxypropylene structure. The polyoxyethylene structure is -(OCH 2 CH 2 )n-, where n is preferably an integer of 2 or more, and more preferably an integer of 2 to 10.

[0131] In formulas (iv) to (vi), Z 1 represents a functional group capable of forming an interaction with the magnetic particles other than the graft chain, and is preferably a carboxylic acid group or a tertiary amino group, more preferably a carboxylic acid group.

[0132] In formula (vi), R 14 , R 15 , and R 16 each independently represents a hydrogen atom, a halogen atom (e.g., a fluorine atom, a chlorine atom, a bromine atom, etc.), an alkyl group having 1 to 6 carbon atoms (e.g., a methyl group, an ethyl group, a propyl group, etc.), -Z 1 , or L 1 -Z 1 Here, L 1 and Z 1 is the L in the above 1 and Z 1 The same applies to preferred examples. 14 , R 15 , and R 16 is preferably a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, and more preferably a hydrogen atom.

[0133] As the monomer represented by formula (iv), R 11 , R 12 , and R 13 are each independently a hydrogen atom or a methyl group, and L 1 is a divalent linking group containing an alkylene group or an oxyalkylene structure, 1 is an oxygen atom or an imino group, and Z 1 is a carboxylic acid group. In addition, as the monomer represented by formula (v), R 11 is a hydrogen atom or a methyl group, and L 1 is an alkylene group, and Z 1 Preferred are compounds in which is a carboxylic acid group and Y is a methine group. Further, as the monomer represented by formula (vi), R 14 , R 15 , and R 16 are each independently a hydrogen atom or a methyl group, and Z 1 is a carboxylic acid group.

[0134] Representative examples of the monomers (compounds) represented by formulas (iv) to (vi) are shown below. Examples of the monomer include methacrylic acid, crotonic acid, isocrotonic acid, a reaction product of a compound containing an addition polymerizable double bond and a hydroxyl group in the molecule (e.g., 2-hydroxyethyl methacrylate) with succinic anhydride, a reaction product of a compound containing an addition polymerizable double bond and a hydroxyl group in the molecule with phthalic anhydride, a reaction product of a compound containing an addition polymerizable double bond and a hydroxyl group in the molecule with tetrahydroxyphthalic anhydride, a reaction product of a compound containing an addition polymerizable double bond and a hydroxyl group in the molecule with trimellitic anhydride, a reaction product of a compound containing an addition polymerizable double bond and a hydroxyl group in the molecule with pyromellitic anhydride, acrylic acid, acrylic acid dimer, acrylic acid oligomer, maleic acid, itaconic acid, fumaric acid, 4-vinylbenzoic acid, vinylphenol, and 4-hydroxyphenylmethacrylamide.

[0135] The content of the repeating unit containing a functional group capable of forming an interaction with the magnetic particles is, in terms of the interaction with the magnetic particles, stability over time, and permeability into the developer, preferably 0.05 to 90 mass %, more preferably 1.0 to 80 mass %, and even more preferably 10 to 70 mass %, relative to the total mass of resin A.

[0136] Ethylenically unsaturated groups Resin A may contain an ethylenically unsaturated group. The ethylenically unsaturated group is not particularly limited, but examples thereof include a (meth)acryloyl group, a vinyl group, and a styryl group, with a (meth)acryloyl group being preferred. Resin A preferably contains a repeating unit containing an ethylenically unsaturated group in the side chain, and more preferably contains a repeating unit containing an ethylenically unsaturated group in the side chain and derived from a (meth)acrylate (hereinafter also referred to as a "(meth)acrylic repeating unit containing an ethylenically unsaturated group in the side chain"). The (meth)acrylic repeating unit containing an ethylenically unsaturated group in the side chain can be obtained, for example, by adding an ethylenically unsaturated compound containing a glycidyl group or an alicyclic epoxy group to the carboxylic acid group in the resin A containing a (meth)acrylic repeating unit containing a carboxylic acid group. By reacting the ethylenically unsaturated group (glycidyl group or alicyclic epoxy group) introduced in this way, a (meth)acrylic repeating unit containing an ethylenically unsaturated group in the side chain can be obtained.

[0137] When the resin A contains a repeating unit containing an ethylenically unsaturated group, the content thereof is preferably from 30 to 70 mass %, and more preferably from 40 to 60 mass %, based on the total mass of the resin A in mass terms.

[0138] Other repeating units Furthermore, for the purpose of improving various performance properties such as film-forming ability, resin A may further contain other repeating units having various functions different from the repeating units containing graft chains, hydrophobic repeating units, and repeating units containing functional groups capable of forming interactions with magnetic particles, as long as the effects of the present invention are not impaired. Examples of such other repeating units include repeating units derived from radically polymerizable compounds selected from acrylonitriles and methacrylonitriles. Resin A may use one or more of these other repeating units, and the content thereof, calculated on a mass basis, is preferably from 0 to 80 mass %, more preferably from 10 to 60 mass %, based on the total mass of resin A.

[0139] Physical properties of Resin A The acid value of resin A is not particularly limited, but is, for example, preferably 0 to 400 mgKOH / g, more preferably 10 to 350 mgKOH / g, further preferably 30 to 300 mgKOH / g, and particularly preferably in the range of 50 to 200 mgKOH / g. If the acid value of resin A is 50 mgKOH / g or more, the sedimentation stability of the magnetic particles can be further improved.

[0140] In this specification, the acid value can be calculated, for example, from the average content of acid groups in a compound. Also, a resin having a desired acid value can be obtained by changing the content of repeating units containing an acid group in the resin.

[0141] The weight average molecular weight of the resin A is not particularly limited, but is preferably, for example, 3,000 or more, more preferably 4,000 or more, even more preferably 5,000 or more, and particularly preferably 6,000 or more. The upper limit is, for example, preferably 300,000 or less, more preferably 200,000 or less, even more preferably 100,000 or less, and particularly preferably 50,000 or less. Resin A can be synthesized based on a known method.

[0142] As specific examples of Resin A, reference can be made to the polymer compounds described in paragraphs 0127 to 0129 of JP-A No. 2013-249417, the contents of which are incorporated herein by reference.

[0143] Furthermore, as the resin A, the graft copolymers described in paragraphs 0037 to 0115 of JP 2010-106268 A (corresponding paragraphs 0075 to 0133 of US 2011 / 0124824) can also be used, the contents of which are incorporated herein by reference.

[0144] (Aggregation control agent) The dispersing resin may include an aggregation control agent. The aggregation control agent has the function of binding to relatively dense aggregates such as magnetic particles, and further dispersing other optional components (e.g., alkali-soluble resins, etc.) in the composition to create bulky aggregates. When the dispersion resin contains an aggregation control agent, the magnetic particles in the composition are prevented from forming a hard cake and bulkier aggregates are formed, which can improve redispersibility.

[0145] The aggregation control agent may, for example, be a cellulose derivative. Examples of the cellulose derivatives include carboxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, hydroxypropyl ethyl cellulose, and salts thereof.

[0146] When the composition contains an aggregation control agent, the content of the aggregation control agent is preferably from 0.1 to 20 mass %, particularly preferably from 0.5 to 10 mass %, based on the total mass of the composition.

[0147] (Aggregation and dispersant) The dispersing resin may be an agglomerating dispersant. The aggregating dispersant has the function of adsorbing to the surface of the magnetic particles, separating the magnetic particles from each other, while maintaining the distance between the magnetic particles at a certain level or more through the interaction between the dispersants, thereby preventing the magnetic particles from aggregating directly with each other. As a result, the aggregation of the magnetic particles is suppressed, and even if an aggregate is formed, the aggregate has a relatively low density. Furthermore, other components (e.g., alkali-soluble resin, etc.) optionally contained in the composition can be dispersed in the composition to form a bulky aggregate, which can improve redispersibility.

[0148] As the flocculating dispersant, an alkylol ammonium salt of a polybasic acid is preferred. The polybasic acid may have two or more acid groups, and examples thereof include acidic polymers containing repeating units having an acid group (e.g., polyacrylic acid, polymethacrylic acid, polyvinylsulfonic acid, polyphosphoric acid, etc.). Other examples of polybasic acids include polymers obtained by polymerizing unsaturated fatty acids such as crotonic acid. Alkylolammonium salts of polybasic acids are obtained by reacting these polybasic acids with alkylolammonium. The salts obtained by such reactions usually contain the following partial structure: -C(=O)-N(-R 1 )(-R 2 -OH) Here, R 1 is an alkyl group, R 2 is an alkylene group. The alkylol ammonium salt of a polybasic acid is preferably a polymer containing a plurality of the above partial structures. When the alkylol ammonium salt of a polybasic acid is a polymer, the weight average molecular weight is preferably 1,000 to 100,000, more preferably 5,000 to 20,000. The polymer of the alkylol ammonium salt of a polybasic acid is bonded to the surface of the magnetic particles and is also hydrogen bonded to other flocculating dispersant molecules, so that the main chain structure of the polymer can penetrate between the magnetic particles and separate the magnetic particles from each other.

[0149] One of the preferred embodiments of the flocculating dispersant is amide wax, which is a dehydration condensation product of at least any acid selected from (a) saturated aliphatic monocarboxylic acids and hydroxyl group-containing aliphatic monocarboxylic acids, and (b) polybasic acids, and (c) at least any amine selected from diamines and tetraamines. The above (a) to (c) are preferably used in such a manner that the molar ratio of (a):(b):(c)=1-3:0-5:1-6.

[0150] The saturated aliphatic monocarboxylic acids preferably have a carbon number of 12 to 22. Specific examples include lauric acid, myristic acid, pentadecylic acid, palmitic acid, margaric acid, stearic acid, nonadecanoic acid, arachidic acid, and behenic acid. The hydroxyl group-containing aliphatic monocarboxylic acids preferably have a carbon number of 12 to 22. Specific examples include 12-hydroxystearic acid and dihydroxystearic acid. These saturated aliphatic monocarboxylic acids and hydroxyl group-containing aliphatic monocarboxylic acids may be used alone or in combination.

[0151] The polybasic acids are preferably dibasic or higher carboxylic acids having 2 to 12 carbon atoms, and more preferably dicarboxylic acids. Examples of such dicarboxylic acids include aliphatic dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, 1,10-decanedicarboxylic acid, and 1,12-dodecanedicarboxylic acid; aromatic dicarboxylic acids such as phthalic acid, isophthalic acid, and terephthalic acid; and alicyclic dicarboxylic acids such as 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, and cyclohexylsuccinic acid. These polybasic acids may be used alone or in combination.

[0152] The diamines preferably have a carbon number of 2 to 14. Specific examples include ethylenediamine, 1,3-propanediamine, 1,4-butanediamine, hexamethylenediamine, metaxylenediamine, tolylenediamine, paraxylenediamine, phenylenediamine, isophoronediamine, 1,10-decanediamine, 1,12-dodecanediamine, 4,4-diaminodicyclohexylmethane, and 4,4-diaminodiphenylmethane. The tetraamines preferably have a carbon number of 2 to 14. Specific examples include butane-1,1,4,4-tetraamine and pyrimidine-2,4,5,6-tetraamine. These diamines and tetraamines may be used alone or in combination.

[0153] The amount of diamines and tetraamines is adjusted according to the number of moles of saturated aliphatic monocarboxylic acid or hydroxyl group-containing aliphatic monocarboxylic acid and the number of moles of polybasic acids so that the total number of carboxyl groups and the total number of amino groups are equivalent. For example, when there are n moles (n=0-5) of aliphatic dicarboxylic acid, which is a polybasic acid, for 2 moles of aliphatic monocarboxylic acid, and the number of moles of diamines is (n+1), the acid and amine are equivalent.

[0154] The amide wax is obtained as a mixture of a plurality of compounds having different molecular weights. The amide wax is preferably represented by the following chemical formula (I). The amide wax may be a single compound or a mixture. AC-(BC) m -A···(I) In formula (I), A is a dehydroxylated residue of a saturated aliphatic monocarboxylic acid and / or a hydroxyl group-containing saturated aliphatic monocarboxylic acid, B is a dehydroxylated residue of a polybasic acid, C is a dehydrogenated residue of a diamine and / or a tetraamine, and m is 0≦m≦5.

[0155] One preferred embodiment of the aggregation dispersant is a compound represented by the following formula (II).

[0156] [ka]

[0157] In formula (II), R 1 represents a monovalent linear aliphatic hydrocarbon group having 10 to 25 carbon atoms, R 2 and R 3 each independently represents a divalent aliphatic hydrocarbon group having 2, 4, 6, or 8 carbon atoms, a divalent alicyclic hydrocarbon group having 6 carbon atoms, or a divalent aromatic hydrocarbon group; R 4 represents a divalent aliphatic hydrocarbon group having 1 to 8 carbon atoms, R 5 and R 6 each independently represents a monovalent aliphatic hydrocarbon group having 1 to 3 carbon atoms or a hydroxyalkyl ether group. In formula (II), L 1 ~L 3 each independently represents an amide bond, L 1 and L 3 If -CONH-, then L 2 is -NHCO-, and L 1 and L 3 When is -NHCO-, L 2 is -CONH-.

[0158] R 1is a monovalent linear aliphatic hydrocarbon group having 10 to 25 carbon atoms, and examples thereof include linear alkyl groups such as decyl, lauryl, myristyl, pentadecyl, stearyl, palmityl, nonadecyl, eicosyl, and behenyl groups; linear alkenyl groups such as decenyl, pentadecenyl, oleyl, and eicosenyl groups; and linear alkynyl groups such as pentadecynyl, octadecynyl, and nonadecenyl groups. Among them, R 1 In terms of having an excellent thickening effect and being able to suppress the amount of remaining ash to an extremely low level even when fired at a low temperature, a monovalent linear aliphatic hydrocarbon group having 14 to 25 carbon atoms is preferred, and a monovalent linear aliphatic hydrocarbon group having 18 to 21 carbon atoms is particularly preferred. The linear aliphatic hydrocarbon group is preferably an alkyl group.

[0159] R 2 and R 3 Examples of the divalent aliphatic hydrocarbon group having 2, 4, 6 or 8 carbon atoms include an ethylene group, an n-butylene group, an n-hexylene group, and an n-octylene group. R 2 and R 3 Examples of the divalent alicyclic hydrocarbon group having 6 carbon atoms include a 1,4-cyclohexylene group, a 1,3-cyclohexylene group, and a 1,2-cyclohexylene group. R 2 and R 3 Examples of the divalent aromatic hydrocarbon group in include arylene groups having 6 to 10 carbon atoms, such as a 1,4-phenylene group, a 1,3-phenylene group, and a 1,2-phenylene group.

[0160] Among them, R 2 and R 3 In terms of excellent thickening effect, is preferably a divalent aliphatic hydrocarbon group having 2, 4, 6 or 8 carbon atoms, more preferably a divalent aliphatic hydrocarbon group having 2, 4 or 6 carbon atoms, still more preferably a divalent aliphatic hydrocarbon group having 2 or 4 carbon atoms, and particularly preferably a divalent aliphatic hydrocarbon group having 2 carbon atoms. The divalent aliphatic hydrocarbon group is preferably a linear alkylene group.

[0161] R 4 represents a divalent aliphatic hydrocarbon group having 1 to 8 carbon atoms, and among these, a linear or branched alkylene group is preferred, with a linear alkylene group being particularly preferred, in that it has an excellent thickening effect. Also, R 4 The divalent aliphatic hydrocarbon group in has 1 to 8 carbon atoms, and from the viewpoint of excellent thickening effect, it is preferably 1 to 7, more preferably 3 to 7, further preferably 3 to 6, and particularly preferably 3 to 5. Therefore, R 4 is preferably a linear or branched alkylene group having 1 to 8 carbon atoms, more preferably a linear alkylene group having 1 to 7 carbon atoms, still more preferably a linear alkylene group having 3 to 7 carbon atoms, particularly preferably a linear alkylene group having 3 to 6 carbon atoms, and most preferably a linear alkylene group having 3 to 5 carbon atoms.

[0162] R 5 and R 6 Examples of the monovalent aliphatic hydrocarbon group having 1 to 3 carbon atoms include linear or branched alkyl groups having 1 to 3 carbon atoms, such as a methyl group, an ethyl group, a propyl group, or an isopropyl group; linear or branched alkenyl groups having 2 to 3 carbon atoms, such as a vinyl group, a 1-methylvinyl group, or a 2-propenyl group; and linear or branched alkynyl groups having 2 to 3 carbon atoms, such as an ethynyl group or a propynyl group.

[0163] R 5 and R 6 Examples of the hydroxyalkyl ether group in the formula (I) include mono- or di(hydroxy)C groups such as a 2-hydroxyethoxy group, a 2-hydroxypropoxy group, and a 2,3-dihydroxypropoxy group. 1-3 Examples of such groups include alkyl ether groups.

[0164] Among them, R 5 and R 6 are each independently preferably a monovalent aliphatic hydrocarbon group having 1 to 3 carbon atoms, more preferably a linear or branched alkyl group having 1 to 3 carbon atoms, still more preferably a linear alkyl group having 1 to 3 carbon atoms, and particularly preferably a methyl group.

[0165] As the compound represented by formula (II), the compounds represented by the following formulae (II-1) to (II-9) are preferred.

[0166] [ka]

[0167] Examples of the flocculating dispersant include ANTI-TERRA-203, 204, 206, and 250 (all trade names, manufactured by BYK); ANTI-TERRA-U (trade name, manufactured by BYK); DISPER BYK-102, 180, and 191 (all trade names, manufactured by BYK); BYK-P105 (trade name, manufactured by BYK); TEGO Disper 630 and 700 (all trade names, manufactured by Evonik Degussa Japan); TALENE VA-705B (trade name, manufactured by Kyoeisha Chemical Co., Ltd.); and FLOWNON RCM-300TL (trade name, manufactured by Kyoeisha Chemical Co., Ltd., Amide Wax).

[0168] When the composition contains an aggregating dispersant, the content of the aggregating dispersant is preferably from 0.1 to 20 mass %, particularly preferably from 0.5 to 10 mass %, based on the total mass of the composition.

[0169] <Alkali-soluble resin> The resin in the present invention may contain an alkali-soluble resin. In this specification, the alkali-soluble resin means a resin containing a group that promotes alkali solubility (an alkali-soluble group, for example, an acid group such as a carboxylic acid group), and means a resin different from the resin A already described.

[0170] Examples of the alkali-soluble resin include resins containing at least one alkali-soluble group in the molecule, such as polyhydroxystyrene resins, polysiloxane resins, (meth)acrylic resins, (meth)acrylamide resins, (meth)acrylic / (meth)acrylamide copolymers, epoxy resins, and polyimide resins.

[0171] Specific examples of alkali-soluble resins include copolymers of unsaturated carboxylic acids and ethylenically unsaturated compounds. The unsaturated carboxylic acid is not particularly limited, but examples thereof include monocarboxylic acids such as (meth)acrylic acid, crotonic acid, and vinylacetic acid; dicarboxylic acids such as itaconic acid, maleic acid, and fumaric acid, or acid anhydrides thereof; and polycarboxylic acid monoesters such as mono(2-(meth)acryloyloxyethyl)phthalate.

[0172] Examples of the copolymerizable ethylenically unsaturated compound include methyl (meth)acrylate, etc. Compounds described in paragraph 0027 of JP-A-2010-97210 and paragraphs 0036-0037 of JP-A-2015-68893 can also be used, and the contents of the above are incorporated herein by reference.

[0173] In addition, a copolymerizable ethylenically unsaturated compound having an ethylenically unsaturated group in a side chain may be used in combination. In other words, the alkali-soluble resin may contain a repeating unit having an ethylenically unsaturated group in a side chain. The ethylenically unsaturated group contained in the side chain is preferably a (meth)acrylic acid group. A repeating unit containing an ethylenically unsaturated group in a side chain can be obtained, for example, by subjecting a carboxylic acid group of a (meth)acrylic repeating unit containing a carboxylic acid group to an addition reaction with an ethylenically unsaturated compound containing a glycidyl group or an alicyclic epoxy group.

[0174] The alkali-soluble resin is also preferably an alkali-soluble resin containing a curable group. Examples of the curable group include, but are not limited to, ethylenically unsaturated groups (e.g., (meth)acryloyl groups, vinyl groups, styryl groups, etc.) and cyclic ether groups (e.g., epoxy groups, oxetanyl groups, etc.). Among these, the curable group is preferably an ethylenically unsaturated group, and more preferably a (meth)acryloyl group, in terms of the ability to control polymerization by radical reaction. The alkali-soluble resin containing a curable group is preferably an alkali-soluble resin having a curable group in a side chain, etc. Examples of the alkali-soluble resin containing a curable group include Dianaru NR series (manufactured by Mitsubishi Rayon Co., Ltd.), Photomer 6173 (COOH-containing polyurethane acrylic oligomer, manufactured by Diamond Shamrock Co., Ltd.), Viscoat R-264, KS Resist 106 (all manufactured by Osaka Organic Chemical Industry Co., Ltd.), Cyclomer P series (e.g., ACA230AA), Plaxel CF200 series (all manufactured by Daicel Corporation), Ebecryl 3800 (manufactured by Daicel-Allnex Corporation), and Acricur RD-F8 (manufactured by Nippon Shokubai Co., Ltd.).

[0175] Examples of the alkali-soluble resin include radical polymers having a carboxylic acid group in the side chain described in JP-A-59-44615, JP-B-54-34327, JP-B-58-12577, JP-B-54-25957, JP-A-54-92723, JP-A-59-53836, and JP-A-59-71048; Examples of binder resins that can be used include acetal-modified polyvinyl alcohol-based binder resins containing an alkali-soluble group as described in JP 1-318463 A; polyvinylpyrrolidone; polyethylene oxide; alcohol-soluble nylon, and polyethers which are reaction products of 2,2-bis-(4-hydroxyphenyl)-propane and epichlorohydrin; and polyimide resins as described in WO 2008 / 123097 A.

[0176] As the alkali-soluble resin, for example, the compounds described in paragraphs 0225 to 0245 of JP-A-2016-75845 can also be used, the contents of which are incorporated herein by reference.

[0177] As the alkali-soluble resin, a polyimide precursor can also be used. The polyimide precursor refers to a resin obtained by subjecting a compound containing an acid anhydride group and a diamine compound to an addition polymerization reaction at 40 to 100°C. Specific examples of the polyimide precursor include compounds described in paragraphs 0011 to 0031 of JP 2008-106250 A, compounds described in paragraphs 0022 to 0039 of JP 2016-122101 A, compounds described in paragraphs 0061 to 0092 of JP 2016-68401 A, resins described in paragraph 0050 of JP 2014-137523 A, resins described in paragraph 0058 of JP 2015-187676 A, and resins described in paragraphs 0012 to 0013 of JP 2014-106326 A, the contents of which are incorporated herein by reference.

[0178] As the alkali-soluble resin, a copolymer of [benzyl (meth)acrylate / (meth)acrylic acid / if necessary, other addition-polymerizable vinyl monomer] and a copolymer of [allyl (meth)acrylate / (meth)acrylic acid / if necessary, other addition-polymerizable vinyl monomer] are preferable because they have an excellent balance of film strength, sensitivity, and developability. The other addition-polymerizable vinyl monomers may be used alone or in combination of two or more kinds. The copolymer preferably contains a curable group, and more preferably contains an ethylenically unsaturated group such as a (meth)acryloyl group, in order to provide a cured film with better moisture resistance. For example, a curable group may be introduced into the copolymer by using a monomer having a curable group as the other addition polymerizable vinyl monomer. Also, a curable group (preferably an ethylenically unsaturated group such as a (meth)acryloyl group) may be introduced into a part or all of one or more of the units derived from (meth)acrylic acid and / or the other addition polymerizable vinyl monomer in the copolymer. Examples of the other addition-polymerizable vinyl monomers include methyl (meth)acrylate, styrene-based monomers (such as hydroxystyrene), and ether dimers. Examples of the ether dimer include a compound represented by the following general formula (ED1) and a compound represented by the following general formula (ED2).

[0179] [ka]

[0180] In general formula (ED1), R 1 and R 2 each independently represents a hydrogen atom or a hydrocarbon group having 1 to 25 carbon atoms.

[0181] [ka]

[0182] In the general formula (ED2), R represents a hydrogen atom or an organic group having a carbon number of 1 to 30. Specific examples of the general formula (ED2) can be found in JP-A-2010-168539.

[0183] For specific examples of the ether dimer, see, for example, paragraph 0317 of JP 2013-29760 A, the contents of which are incorporated herein by reference. The ether dimer may be one type only, or two or more types.

[0184] The acid value of the alkali-soluble resin is not particularly limited, but in general, it is preferably from 30 to 500 mgKOH / g, and more preferably from 50 to 200 mgKOH / g or more.

[0185] When the composition contains an alkali-soluble resin, the content of the alkali-soluble resin is preferably from 0.1 to 40 mass %, more preferably from 0.5 to 30 mass %, particularly preferably from 1 to 20 mass %, based on the total mass of the composition.

[0186] 〔solvent〕 The composition contains a solvent. Examples of the solvent include water and organic solvents, and organic solvents are preferred. From the viewpoint of coatability, the boiling point of the solvent is preferably from 100 to 400° C., more preferably from 150 to 300° C., and particularly preferably from 170 to 250° C. In this specification, the boiling point means the normal boiling point, unless otherwise specified.

[0187] Examples of the organic solvent include acetone, methyl ethyl ketone, cyclohexane, ethyl acetate, ethylene dichloride, tetrahydrofuran, toluene, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol dimethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, acetylacetone, cyclohexanone, cyclopentanone, diacetone alcohol, ethylene glycol monomethyl ether acetate, ethylene glycol ethyl ether acetate, ethylene glycol monoisopropyl ether, and ethylene glycol monobutyl ether. Examples of the alkyl ether acetate include, but are not limited to, butyl acetate, 1,4-butanediol diacetate, 3-methoxypropanol, methoxymethoxyethanol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, 3-methoxypropyl acetate, N,N-dimethylformamide, dimethyl sulfoxide, γ-butyrolactone, butyl acetate, methyl lactate, N-methyl-2-pyrrolidone, and ethyl lactate.

[0188] The content of the solvent is preferably from 1 to 60 mass %, more preferably from 2 to 50 mass %, and particularly preferably from 3 to 40 mass %, based on the total mass of the composition, in that the effects of the present invention are more excellent.

[0189] [Polymerization initiator] The composition may contain a polymerization initiator. The polymerization initiator is not particularly limited, and a known polymerization initiator can be used. Examples of the polymerization initiator include a photopolymerization initiator and a thermal polymerization initiator, and a photopolymerization initiator is preferred. The polymerization initiator is preferably a so-called radical polymerization initiator. The content of the polymerization initiator in the composition is not particularly limited, but is preferably 0.5 to 15 mass %, more preferably 1.0 to 10 mass %, and even more preferably 1.5 to 8.0 mass %, based on the total solid content of the composition.

[0190] <Thermal polymerization initiator> Examples of the thermal polymerization initiator include azo compounds such as 2,2'-azobisisobutyronitrile (AIBN), 3-carboxypropionitrile, azobismalononitrile, and dimethyl-(2,2')-azobis(2-methylpropionate) [V-601], and organic peroxides such as benzoyl peroxide, lauroyl peroxide, and potassium persulfate. Specific examples of the polymerization initiator include those described on pages 65 to 148 of "Ultraviolet Curing System" by Kiyomi Kato (published by Sogo Gijutsu Center Co., Ltd. in 1989).

[0191] <Photopolymerization initiator> The photopolymerization initiator is not particularly limited as long as it can initiate polymerization of the polymerizable compound, and a known photopolymerization initiator can be used. For example, the photopolymerization initiator is preferably a photopolymerization initiator having photosensitivity to the ultraviolet region to the visible light region. In addition, it may be an activator that generates an active radical by reacting with a photoexcited sensitizer, or an initiator that initiates cationic polymerization according to the type of polymerizable compound. The photopolymerization initiator preferably contains at least one compound having a molar absorption coefficient of at least 50 within a range of 300 to 800 nm (more preferably 330 to 500 nm).

[0192] Examples of the photopolymerization initiator include halogenated hydrocarbon derivatives (e.g., compounds containing a triazine skeleton, compounds containing an oxadiazole skeleton, etc.), acylphosphine compounds such as acylphosphine oxides, hexaarylbiimidazoles, oxime compounds such as oxime derivatives, organic peroxides, thio compounds, ketone compounds, aromatic onium salts, aminoacetophenone compounds, and hydroxyacetophenones. Specific examples of photopolymerization initiators can be found in, for example, paragraphs

[0265] to

[0268] of JP-A-2013-29760, the contents of which are incorporated herein by reference.

[0193] More specifically, for example, the aminoacetophenone-based initiators described in JP-A-10-291969 and the acylphosphine-based initiators described in Japanese Patent No. 4225898 can also be used as the photopolymerization initiator. As the hydroxyacetophenone compound, for example, IRGACURE-184, DAROCUR-1173, IRGACURE-500, IRGACURE-2959, and IRGACURE-127 (trade names, all manufactured by BASF) can be used. As the aminoacetophenone compound, for example, commercially available products IRGACURE-907, IRGACURE-369, and IRGACURE-379EG (trade names, all manufactured by BASF) can be used. As the aminoacetophenone compound, compounds described in JP-A-2009-191179, which have an absorption wavelength matching a long-wavelength light source such as a wavelength of 365 nm or 405 nm, can also be used. As the acylphosphine compound, commercially available products IRGACURE-819 and IRGACURE-TPO (trade names, both manufactured by BASF) can be used.

[0194] As the photopolymerization initiator, an oxime ester-based polymerization initiator (oxime compound) is more preferable. In particular, an oxime compound is preferable because it has high sensitivity and high polymerization efficiency, and it is easy to design the content of the coloring material in the composition to be high. Specific examples of the oxime compound that can be used include the compounds described in JP-A-2001-233842, JP-A-2000-80068, and JP-A-2006-342166. Examples of the oxime compound include 3-benzoyloxyiminobutan-2-one, 3-acetoxyiminobutan-2-one, 3-propionyloxyiminobutan-2-one, 2-acetoxyiminopentan-3-one, 2-acetoxyimino-1-phenylpropan-1-one, 2-benzoyloxyimino-1-phenylpropan-1-one, 3-(4-toluenesulfonyloxy)iminobutan-2-one, and 2-ethoxycarbonyloxyimino-1-phenylpropan-1-one. Further examples include the compounds described in J.C.S. Perkin II (1979) pp. 1653-1660, J.C.S. Perkin II (1979) pp. 156-162, Journal of Photopolymer Science and Technology (1995) pp. 202-232, JP-A No. 2000-66385, and JP-T No. 2004-534797. Commercially available products include IRGACURE-OXE01 (manufactured by BASF), IRGACURE-OXE02 (manufactured by BASF), IRGACURE-OXE03 (manufactured by BASF), and IRGACURE-OXE04 (manufactured by BASF). TR-PBG-304 (manufactured by Changzhou Strong Electronic New Materials Co., Ltd.), Adeka Arcles NCI-831, Adeka Arcles NCI-930 (manufactured by ADEKA), and N-1919 (carbazole oxime ester skeleton-containing photoinitiator (manufactured by ADEKA)) can also be used.

[0195] In addition, as oxime compounds other than those described above, the compound described in JP-T-2009-519904 A in which an oxime is linked to the N-position of the carbazole; the compound described in U.S. Pat. No. 7,626,957 A in which a heterosubstituent is introduced at the benzophenone moiety; the compounds described in JP-A-2010-15025 A and U.S. Patent Publication No. 2009-292039 in which a nitro group is introduced at the dye moiety; the ketoxime compounds described in WO-A-2009-131189; and the compound described in U.S. Pat. No. 7,556,910 in which a triazine skeleton and an oxime skeleton are contained in the same molecule; and the compound described in JP-A-2009-221114 A in which an absorption maximum is at 405 nm and which has good sensitivity to a g-line light source; etc. may be used. For example, see paragraphs 0274 to 0275 of JP 2013-29760 A, the contents of which are incorporated herein by reference. Specifically, the oxime compound is preferably a compound represented by the following formula (OX-1): The oxime compound may be an oxime compound in which the NO bond is an (E) form, an oxime compound in which the NO bond is an (Z) form, or a mixture of the (E) form and the (Z) form.

[0196] [ka]

[0197] In formula (OX-1), R and B each independently represent a monovalent substituent, A represents a divalent organic group, and Ar represents an aryl group. In formula (OX-1), the monovalent substituent represented by R is preferably a monovalent nonmetallic atomic group. Examples of the monovalent nonmetallic atomic group include an alkyl group, an aryl group, an acyl group, an alkoxycarbonyl group, an aryloxycarbonyl group, a heterocyclic group, an alkylthiocarbonyl group, and an arylthiocarbonyl group. These groups may have one or more substituents. The aforementioned substituents may be further substituted with other substituents. Examples of the substituent include a halogen atom, an aryloxy group, an alkoxycarbonyl group or an aryloxycarbonyl group, an acyloxy group, an acyl group, an alkyl group, and an aryl group. In formula (OX-1), the monovalent substituent represented by B is preferably an aryl group, a heterocyclic group, an arylcarbonyl group, or a heterocyclic carbonyl group, and more preferably an aryl group or a heterocyclic group. These groups may have one or more substituents. Examples of the substituent include the above-mentioned substituents. In formula (OX-1), the divalent organic group represented by A is preferably an alkylene group, a cycloalkylene group, or an alkynylene group having 1 to 12 carbon atoms. These groups may have one or more substituents. Examples of the substituents include the substituents described above.

[0198] As the photopolymerization initiator, an oxime compound containing a fluorine atom can also be used. Specific examples of the oxime compound containing a fluorine atom include the compounds described in JP-A-2010-262028; compounds 24, 36 to 40 described in JP-T-2014-500852; and compound (C-3) described in JP-A-2013-164471. The contents of these compounds are incorporated herein by reference.

[0199] As the photopolymerization initiator, compounds represented by the following general formulas (1) to (4) can also be used.

[0200] [ka]

[0201] [ka]

[0202] In formula (1), R 1 and R 2 each independently represents an alkyl group having 1 to 20 carbon atoms, an alicyclic hydrocarbon group having 4 to 20 carbon atoms, an aryl group having 6 to 30 carbon atoms, or an arylalkyl group having 7 to 30 carbon atoms; R 1 and R 2 When R is a phenyl group, the phenyl groups may be bonded to each other to form a fluorene group, 3 and R 4 each independently represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 30 carbon atoms, an arylalkyl group having 7 to 30 carbon atoms, or a heterocyclic group having 4 to 20 carbon atoms, and X represents a direct bond or a carbonyl group.

[0203] In formula (2), R 1 , R 2 , R 3 , and R 4 is R in formula (1). 1 , R 2 , R 3 , and R 4 is synonymous with R 5 -R 6 , -OR 6 , -SR 6 , -COR 6 , -CONR 6 R 6 , -NR 6 COR 6 , -OCOR 6 , -COOR 6 , -SCOR 6 , -OCSR 6, -COSR 6 , -CSOR 6 , -CN, a halogen atom, or a hydroxyl group; R 6 represents an alkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 30 carbon atoms, an arylalkyl group having 7 to 30 carbon atoms, or a heterocyclic group having 4 to 20 carbon atoms; X represents a direct bond or a carbonyl group; and a represents an integer of 0 to 4.

[0204] In formula (3), R 1 represents an alkyl group having 1 to 20 carbon atoms, an alicyclic hydrocarbon group having 4 to 20 carbon atoms, an aryl group having 6 to 30 carbon atoms, or an arylalkyl group having 7 to 30 carbon atoms; R 3 and R 4 each independently represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 30 carbon atoms, an arylalkyl group having 7 to 30 carbon atoms, or a heterocyclic group having 4 to 20 carbon atoms, and X represents a direct bond or a carbonyl group.

[0205] In formula (4), R 1 , R 3 , and R 4 is R in Eq. (3). 1 , R 3 , and R 4 is synonymous with R 5 -R 6 , -OR 6 , -SR 6 , -COR 6 , -CONR 6 R 6 , -NR 6 COR 6 , -OCOR 6 , -COOR 6 , -SCOR 6 , -OCSR 6 , -COSR 6 , -CSOR 6 , -CN, a halogen atom, or a hydroxyl group; R 6 represents an alkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 30 carbon atoms, an arylalkyl group having 7 to 30 carbon atoms, or a heterocyclic group having 4 to 20 carbon atoms; X represents a direct bond or a carbonyl group; and a represents an integer of 0 to 4.

[0206] In the above formulas (1) and (2), R 1 and R 2 is preferably a methyl group, an ethyl group, an n-propyl group, an i-propyl group, a cyclohexyl group, or a phenyl group. 3 R is preferably a methyl group, an ethyl group, a phenyl group, a tolyl group, or a xylyl group. 4 R is preferably an alkyl group having 1 to 6 carbon atoms or a phenyl group. 5 is preferably a methyl group, an ethyl group, a phenyl group, a tolyl group, or a naphthyl group. X is preferably a direct bond. In addition, in the above formulas (3) and (4), R 1 is preferably a methyl group, an ethyl group, an n-propyl group, an i-propyl group, a cyclohexyl group, or a phenyl group. 3 R is preferably a methyl group, an ethyl group, a phenyl group, a tolyl group, or a xylyl group. 4 R is preferably an alkyl group having 1 to 6 carbon atoms or a phenyl group. 5 is preferably a methyl group, an ethyl group, a phenyl group, a tolyl group, or a naphthyl group. X is preferably a direct bond. Specific examples of the compounds represented by formula (1) and formula (2) include the compounds described in paragraphs 0076 to 0079 of JP2014-137466A, the contents of which are incorporated herein by reference.

[0207] Specific examples of oxime compounds that can be preferably used in the above composition are shown below. Among the oxime compounds shown below, the oxime compound represented by the general formula (C-13) is more preferred. In addition, as the oxime compound, compounds described in Table 1 of International Publication No. 2015-036910 can also be used, the contents of which are incorporated herein by reference.

[0208] [ka]

[0209] [ka]

[0210] The oxime compound preferably has a maximum absorption wavelength in the wavelength region of 350 to 500 nm, more preferably has a maximum absorption wavelength in the wavelength region of 360 to 480 nm, and further preferably has high absorbance at wavelengths of 365 nm and 405 nm. The molar absorption coefficient of the oxime compound at 365 nm or 405 nm is preferably from 1,000 to 300,000, more preferably from 2,000 to 300,000, and even more preferably from 5,000 to 200,000, from the viewpoint of sensitivity. The molar absorption coefficient of a compound can be measured by a known method. For example, it is preferable to measure it using an ultraviolet-visible spectrophotometer (Varian Cary-5 spectrophotometer) at a concentration of 0.01 g / L using ethyl acetate. Two or more kinds of photopolymerization initiators may be used in combination, if necessary.

[0211] In addition, as the photopolymerization initiator, the compounds described in paragraph 0052 of JP-A-2008-260927, paragraphs 0033 to 0037 of JP-A-2010-97210, and paragraph 0044 of JP-A-2015-68893 can also be used, the contents of which are incorporated herein by reference.

[0212] [Polymerizable compound] The composition of the present invention may contain a polymerizable compound. In this specification, the polymerizable compound means a compound which polymerizes under the action of the above-mentioned polymerization initiator, and means a component different from the above-mentioned resin in the composition of the present invention.

[0213] The content of the polymerizable compound in the composition is not particularly limited, but is preferably from 1 to 25 mass %, more preferably from 1 to 20 mass %, and even more preferably from 3 to 15 mass %, based on the total solid content of the composition. The molecular weight (or weight average molecular weight) of the polymerizable compound is not particularly limited, but is preferably 2000 or less.

[0214] The polymerizable compound is preferably a compound containing a group containing an ethylenically unsaturated bond (hereinafter, also simply referred to as an "ethylenically unsaturated group"). That is, the composition of the present invention preferably contains a low molecular weight compound containing an ethylenically unsaturated group as a polymerizable compound. The polymerizable compound is preferably a compound containing one or more ethylenically unsaturated bonds, more preferably a compound containing two or more, even more preferably a compound containing three or more, and particularly preferably a compound containing five or more. The upper limit is, for example, 15 or less. Examples of the ethylenically unsaturated group include a vinyl group, a (meth)allyl group, and a (meth)acryloyl group.

[0215] As the polymerizable compound, for example, the compounds described in paragraph 0050 of JP-A-2008-260927 and paragraph 0040 of JP-A-2015-68893 can be used, the contents of which are incorporated herein by reference.

[0216] The polymerizable compound may be in any chemical form, such as a monomer, a prepolymer, an oligomer, a mixture thereof, or a polymer thereof. The polymerizable compound is preferably a 3- to 15-functional (meth)acrylate compound, and more preferably a 3- to 6-functional (meth)acrylate compound.

[0217] The polymerizable compound is also preferably a compound containing one or more ethylenically unsaturated groups and having a boiling point of 100° C. or higher under normal pressure. For example, the compounds described in paragraphs

[0227] of JP-A-2013-29760 and paragraphs

[0254] to

[0257] of JP-A-2008-292970 can be referred to, the contents of which are incorporated herein by reference.

[0218] The polymerizable compound is preferably dipentaerythritol triacrylate (commercially available product is KAYARAD D-330; manufactured by Nippon Kayaku Co., Ltd.), dipentaerythritol tetraacrylate (commercially available product is KAYARAD D-320; manufactured by Nippon Kayaku Co., Ltd.), dipentaerythritol penta(meth)acrylate (commercially available product is KAYARAD D-310; manufactured by Nippon Kayaku Co., Ltd.), dipentaerythritol hexa(meth)acrylate (commercially available products are KAYARAD DPHA; manufactured by Nippon Kayaku Co., Ltd., A-DPH-12E; manufactured by Shin-Nakamura Chemical Co., Ltd.), and a structure in which the (meth)acryloyl group of these is mediated by an ethylene glycol residue or a propylene glycol residue (for example, SR454, SR499, commercially available from Sartomer Co., Ltd.). Oligomer types of these can also be used. In addition, NK Ester A-TMMT (pentaerythritol tetraacrylate, manufactured by Shin-Nakamura Chemical Co., Ltd.), KAYARAD RP-1040, KAYARAD DPEA-12LT, KAYARAD DPHA LT, KAYARAD RP-3060, and KAYARAD DPEA-12 (all trade names, manufactured by Nippon Kayaku Co., Ltd.), etc. may also be used. Preferred embodiments of the polymerizable compound are shown below.

[0219] The polymerizable compound may have an acid group such as a carboxylic acid group, a sulfonic acid group, and a phosphoric acid group. As the polymerizable compound containing an acid group, an ester of an aliphatic polyhydroxy compound and an unsaturated carboxylic acid is preferable, and a polymerizable compound in which an acid group is provided by reacting an unreacted hydroxyl group of an aliphatic polyhydroxy compound with a non-aromatic carboxylic anhydride is more preferable, and in this ester, a compound in which the aliphatic polyhydroxy compound is pentaerythritol and / or dipentaerythritol is even more preferable. As a commercially available product, for example, Aronix TO-2349, M-305, M-510, and M-520 manufactured by Toagosei Co., Ltd. can be mentioned.

[0220] The acid value of the polymerizable compound containing an acid group is preferably 0.1 to 40 mgKOH / g, more preferably 5 to 30 mgKOH / g. If the acid value of the polymerizable compound is 0.1 mgKOH / g or more, the development dissolution property is good, and if it is 40 mgKOH / g or less, it is advantageous in terms of production and / or handling. Furthermore, the photopolymerization performance is good and the curing property is excellent.

[0221] In a preferred embodiment, the polymerizable compound is a compound containing a caprolactone structure. The compound containing a caprolactone structure is not particularly limited as long as it contains a caprolactone structure in the molecule, and examples thereof include ε-caprolactone-modified polyfunctional (meth)acrylates obtained by esterifying a polyhydric alcohol such as trimethylolethane, ditrimethylolethane, trimethylolpropane, ditrimethylolpropane, pentaerythritol, dipentaerythritol, tripentaerythritol, glycerin, diglycerol, or trimethylolmelamine with (meth)acrylic acid and ε-caprolactone. Among these, a compound containing a caprolactone structure represented by the following formula (Z-1) is preferred.

[0222] [ka]

[0223] In formula (Z-1), all of the six R's are groups represented by the following formula (Z-2), or 1 to 5 of the six R's are groups represented by the following formula (Z-2), and the remainder are groups represented by the following formula (Z-3).

[0224] [ka]

[0225] In formula (Z-2), R 1 represents a hydrogen atom or a methyl group, m represents the number 1 or 2, and "*" represents a bond.

[0226] [ka]

[0227] In formula (Z-3), R 1 represents a hydrogen atom or a methyl group, and "*" represents a bond.

[0228] Polymerizable compounds containing a caprolactone structure are commercially available from Nippon Kayaku as the KAYARAD DPCA series, for example, and include DPCA-20 (where m=1 in the above formulas (Z-1) to (Z-3), the number of groups represented by formula (Z-2)=2, and R 1 are all hydrogen atoms), DPCA-30 (same formula, m=1, the number of groups represented by formula (Z-2)=3, R 1 are all hydrogen atoms), DPCA-60 (same formula, m=1, the number of groups represented by formula (Z-2)=6, R 1 are all hydrogen atoms), and DPCA-120 (wherein m=2, the number of groups represented by formula (Z-2)=6, R 1 are all hydrogen atoms). In addition, a commercially available polymerizable compound containing a caprolactone structure includes M-350 (trade name) (trimethylolpropane triacrylate) manufactured by Toagosei Co., Ltd.

[0229] As the polymerizable compound, a compound represented by the following formula (Z-4) or (Z-5) can also be used.

[0230] [ka]

[0231] In formulas (Z-4) and (Z-5), E is -((CH 2 ) y CH 2 O)- or ((CH 2 ) y CH(CH 3 )O)-, y represents an integer of 0 to 10, and X represents a (meth)acryloyl group, a hydrogen atom, or a carboxylic acid group. In formula (Z-4), the total number of (meth)acryloyl groups is 3 or 4; m represents an integer of 0 to 10; the sum of the m's is an integer of 0 to 40. In formula (Z-5), the total number of (meth)acryloyl groups is 5 or 6; n represents an integer of 0 to 10; and the sum of the n's is an integer of 0 to 60.

[0232] In formula (Z-4), m is preferably an integer of 0 to 6, and more preferably an integer of 0 to 4. The sum of the m's is preferably an integer of 2 to 40, more preferably an integer of 2 to 16, and further preferably an integer of 4 to 8. In the formula (Z-5), n is preferably an integer of 0 to 6, and more preferably an integer of 0 to 4. The sum of each n is preferably an integer of 3 to 60, more preferably an integer of 3 to 24, and further preferably an integer of 6 to 12. In addition, -((CH 2 ) y CH 2 O)- or ((CH 2 ) y CH(CH 3 )O)- is preferably in a form in which the end on the oxygen atom side is bonded to X.

[0233] The compound represented by formula (Z-4) or formula (Z-5) may be used alone or in combination of two or more. In particular, in formula (Z-5), the form in which all six Xs are acryloyl groups, and in formula (Z-5), the mixture of the compound in which all six Xs are acryloyl groups and the compound in which at least one of the six Xs is a hydrogen atom are preferred. With this configuration, the developability can be further improved.

[0234] The total content of the compound represented by formula (Z-4) or formula (Z-5) in the polymerizable compounds is preferably 20% by mass or more, and more preferably 50% by mass or more. Among the compounds represented by formula (Z-4) or formula (Z-5), pentaerythritol derivatives and / or dipentaerythritol derivatives are more preferred.

[0235] The polymerizable compound may also contain a cardo skeleton. As the polymerizable compound containing a cardo skeleton, a polymerizable compound containing a 9,9-bisarylfluorene skeleton is preferable. Examples of the polymerizable compound containing a cardo skeleton include, but are not limited to, Oncoat EX series (manufactured by Nagase & Co., Ltd.) and OGSOL (manufactured by Osaka Gas Chemicals Co., Ltd.). The polymerizable compound is also preferably a compound containing an isocyanuric acid skeleton as a central core. An example of such a polymerizable compound is NK Ester A-9300 (manufactured by Shin-Nakamura Chemical Co., Ltd.). The content of ethylenically unsaturated groups in the polymerizable compound (meaning the value obtained by dividing the number of ethylenically unsaturated groups in the polymerizable compound by the molecular weight (g / mol) of the polymerizable compound) is preferably 5.0 mmol / g or more. The upper limit is not particularly limited, but is generally 20.0 mmol / g or less.

[0236] As the polymerizable compound, it is also preferable to use an oxacyclo compound. As the oxacyclo compound, a compound having an epoxy group or an oxetanyl group is preferable, and a compound having an epoxy group (epoxy compound) is particularly preferable. Specific examples of such polymerizable compounds include monofunctional or polyfunctional glycidyl ether compounds. Commercially available products include polyfunctional aliphatic glycidyl ether compounds such as Denacol EX-212L, EX-214L, EX-216L, EX-321L, and EX-850L (all manufactured by Nagase ChemteX Corp.). These are low-chlorine products, but non-low-chlorine products such as EX-212, EX-214, EX-216, EX-321, EX-614, and EX-850 can also be used. In addition, a commercially available product such as Celloxide 2021P (manufactured by Daicel Corporation, a multifunctional epoxy monomer) can also be used.

[0237] [Polymerization inhibitor] The composition may also include a polymerization inhibitor. The polymerization inhibitor is not particularly limited, and known polymerization inhibitors can be used. Examples of the polymerization inhibitor include phenol-based polymerization inhibitors (e.g., p-methoxyphenol, 2,5-di-tert-butyl-4-methylphenol, 2,6-di-tert-butyl-4-methylphenol, 4,4'-thiobis(3-methyl-6-t-butylphenol), 2,2'-methylenebis(4-methyl-6-t-butylphenol), 4-methoxynaphthol, etc.); hydroquinone-based polymerization inhibitors (e.g., hydroquinone, 2,6-di-tert-butylhydroquinone, etc.); quinone, etc.); quinone-based polymerization inhibitors (e.g., benzoquinone, etc.); free radical-based polymerization inhibitors (e.g., 2,2,6,6-tetramethylpiperidine 1-oxyl free radical, 4-hydroxy-2,2,6,6-tetramethylpiperidine 1-oxyl free radical, etc.); nitrobenzene-based polymerization inhibitors (e.g., nitrobenzene, 4-nitrotoluene, etc.); and phenothiazine-based polymerization inhibitors (e.g., phenothiazine, 2-methoxyphenothiazine, etc.); and the like. Among these, phenol-based polymerization inhibitors or free radical-based polymerization inhibitors are preferred.

[0238] The effect of the polymerization inhibitor is remarkable when it is used together with a resin containing a curable group. The content of the polymerization inhibitor in the composition is not particularly limited, but is preferably from 0.0001 to 0.5 mass %, more preferably from 0.0001 to 0.2 mass %, and even more preferably from 0.0001 to 0.05 mass %, based on the total solid content of the composition. In addition, the ratio of the content of the polymerization inhibitor to the content of the polymerizable compound in the composition (content of the polymerization inhibitor / content of the polymerizable compound (mass ratio)) is preferably more than 0.0005, more preferably 0.0006 to 0.02, and even more preferably 0.0006 to 0.005.

[0239] [Surfactant] The composition may contain a surfactant. The surfactant contributes to improving the coatability of the composition. When the composition contains a surfactant, the content of the surfactant is preferably from 0.001 to 2.0 mass %, more preferably from 0.005 to 0.5 mass %, and even more preferably from 0.01 to 0.1 mass %, based on the total solid content of the composition.

[0240] Examples of the surfactant include a fluorine-based surfactant, a nonionic surfactant, a cationic surfactant, an anionic surfactant, and a silicone-based surfactant.

[0241] For example, if the composition contains a fluorine-based surfactant, the liquid properties (particularly, fluidity) of the composition are improved. That is, when a film is formed using a composition containing a fluorine-based surfactant, the interfacial tension between the surface to be coated and the coating liquid is reduced, improving the wettability to the surface to be coated, and improving the coatability to the surface to be coated. Therefore, even if a thin film of about several μm is formed with a small amount of liquid, it is effective in that a film of uniform thickness with little thickness unevenness can be more suitably formed.

[0242] The fluorine content in the fluorosurfactant is preferably 3 to 40 mass%, more preferably 5 to 30 mass%, and further preferably 7 to 25 mass%. A fluorosurfactant having a fluorine content within this range is effective in terms of uniformity of the thickness of the coating film and / or liquid saving properties, and also has good solubility in the composition.

[0243] Examples of fluorine-based surfactants include Megafac F171, F172, F173, F176, F177, F141, F142, F143, F144, R30, F437, F475, F479, F482, F554, and F780 (all manufactured by DIC Corporation); Fluorad FC430, FC431, and FC171 (all manufactured by DIC Corporation). manufactured by Sumitomo 3M Limited); Surflon S-382, Surflon SC-101, Surflon SC-103, Surflon SC-104, Surflon SC-105, Surflon SC-1068, Surflon SC-381, Surflon SC-383, Surflon S-393, and Surflon KH-40 (all manufactured by AGC Corporation); and PF636, PF656, PF6320, PF6520, and PF7002 (manufactured by OMNOVA Corporation). A block polymer can also be used as the fluorine-based surfactant, and specific examples include the compounds described in JP-A-2011-89090.

[0244] [Other optional ingredients] The composition may further contain other optional components other than the above-mentioned components, such as a sensitizer, a co-sensitizer, a crosslinking agent (curing agent), a curing accelerator, a heat curing accelerator, a plasticizer, a diluent, a sensitizer, a rubber component, etc. Furthermore, known additives such as an adhesion promoter to the substrate surface and other auxiliaries (e.g., an antifoaming agent, a flame retardant, a leveling agent, a peeling accelerator, an antioxidant, a fragrance, a surface tension adjuster, and a chain transfer agent, etc.) may be added as necessary.

[0245] [Physical Properties of Composition] The viscosity of the composition at 23° C. is preferably 1 to 10,000 Pa·s, more preferably 10 to 5,000 Pa·s, and particularly preferably 50 to 1,000 Pa·s when the shear rate is 0.1 (1 / s), in view of superior sedimentation stability of the magnetic particles. When the shear rate is 1000 (1 / s), the viscosity of the composition at 23°C is preferably 100 Pa s or less, more preferably 50 Pa s or less, and particularly preferably 10 Pa s or less, in terms of superior sedimentation stability of the magnetic particles. When the shear rate is 1000 (1 / s), the lower limit is preferably 0.001 Pa s or more. Here, the viscosity of the composition at 23°C can be obtained by measuring at 23°C using MCR-102 (manufactured by Anton Paar) while increasing the speed from 0.1 / s to 1000 / s.

[0246] [Method of producing the composition] The composition can be prepared by mixing the above-mentioned components by a known mixing method (for example, a mixing method using a stirrer, a homogenizer, a high-pressure emulsifier, a wet grinder, or a wet disperser). In preparing the composition of the present invention, the components may be mixed at once, or each component may be dissolved or dispersed in a solvent and then mixed successively. The order of addition and working conditions when mixing are not particularly limited.

[0247] [Magnetic particle-containing film] The magnetic particle-containing film of the present invention is formed using the magnetic particle-containing composition of the present invention described above. The thickness of the magnetic particle-containing film is preferably from 1 to 10,000 μm, more preferably from 10 to 1,000 μm, and particularly preferably from 15 to 800 μm, in terms of superior magnetic permeability. The magnetic particle-containing film is suitably used as an electronic component such as an antenna or inductor mounted on an electronic communication device or the like.

[0248] [Method for producing a magnetic particle-containing film] The magnetic particle-containing film of the present invention can be obtained, for example, by curing the above-mentioned composition. The method for producing the magnetic particle-containing film is not particularly limited, but preferably includes the following steps. ·Composition layer formation process ·Curing process

[0249] <Composition layer formation process> In the composition layer forming step, a magnetic particle-containing composition is applied onto a substrate (support) to form a layer of the magnetic particle-containing composition (composition layer). As the substrate, for example, a wiring board having an antenna part or an inductor part can be used.

[0250] The magnetic particle-containing composition can be applied to the substrate by various coating methods such as slit coating, inkjet, spin coating, casting, roll coating, and screen printing. The thickness of the composition layer is preferably 1 to 10,000 μm, more preferably 10 to 1,000 μm, and particularly preferably 15 to 800 μm. The composition layer applied to the substrate can be dried (prebaked) at a temperature of 50 to 140° C. for 10 to 1,800 seconds using, for example, a hot plate or an oven.

[0251] <Curing process> The curing step is not particularly limited as long as it can cure the composition layer, and examples thereof include a heat treatment for heating the composition layer and an exposure treatment for irradiating the composition layer with actinic rays or radiation.

[0252] When the heat treatment is carried out, the heat treatment can be carried out continuously or batchwise using a heating means such as a hot plate, a convection oven (hot air circulation type dryer), or a high-frequency heater. The heating temperature in the heat treatment is preferably from 120 to 260°C, particularly preferably from 150 to 240°C. The pre-baking in the composition layer forming step may also serve as the heat treatment in the curing step.

[0253] When exposure treatment is performed, the method of irradiating with actinic rays or radiation is not particularly limited, but it is preferable to irradiate through a photomask having openings in a pattern. The exposure is preferably carried out by irradiation with radiation. Radiation that can be used for exposure is preferably ultraviolet light such as g-line, h-line, or i-line, and a high-pressure mercury lamp is preferred as the light source. The irradiation intensity is 5 to 1500 mJ / cm. 2 is preferable, and 10 to 1000 mJ / cm 2 is more preferred. When the magnetic particle-containing composition contains a thermal polymerization initiator, the composition layer may be heated in the above exposure treatment. The heating temperature is not particularly limited, but is preferably 80 to 250°C. The heating time is not particularly limited, but is preferably from 30 to 300 seconds. In addition, when the composition layer is heated in the exposure treatment, this may also serve as a post-heating step described later. In other words, when the composition layer is heated in the exposure treatment, the method for producing a magnetic particle-containing film does not need to include a post-heating step.

[0254] <Developing process> When an exposure treatment is performed in the curing step, a development step may be further included. The development step is a step of developing the composition layer after exposure to form a magnetic particle-containing film. By this step, the composition layer in the portion not irradiated with light in the exposure treatment is dissolved, and only the photocured portion remains, thereby obtaining a patterned magnetic particle-containing film. The type of developer used in the development step is not particularly limited, but an alkaline developer that does not damage circuits and the like is preferable. The development temperature is, for example, 20 to 30°C. The developing time is, for example, 20 to 90 seconds. In recent years, in order to better remove residues, the developing time may be 120 to 180 seconds. Furthermore, in order to further improve the removability of residues, the developing solution may be shaken off every 60 seconds, and the process of supplying new developing solution may be repeated several times.

[0255] The alkaline developer is preferably an alkaline aqueous solution prepared by dissolving an alkaline compound in water to a concentration of 0.001 to 10% by mass (preferably 0.01 to 5% by mass). Examples of alkaline compounds include sodium hydroxide, potassium hydroxide, sodium carbonate, sodium silicate, sodium metasilicate, aqueous ammonia, ethylamine, diethylamine, dimethylethanolamine, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, benzyltrimethylammonium hydroxide, choline, pyrrole, piperidine, and 1,8-diazabicyclo[5.4.0]-7-undecene (among these, organic alkalis are preferred). When an alkaline developer is used, a washing treatment with water is generally carried out after development.

[0256] <Post bake> When performing exposure treatment in the curing step, it is preferable to perform a heat treatment (post-baking) after the curing step. Post-baking is a heat treatment after development to complete curing. The heating temperature is preferably 240°C or less, more preferably 220°C or less. There is no particular lower limit, but in consideration of efficient and effective treatment, it is preferably 50°C or more, more preferably 100°C or more. The post-baking can be carried out continuously or batchwise using a heating means such as a hot plate, a convection oven (hot air circulation dryer), or a high-frequency heater.

[0257] The post-baking is preferably carried out in an atmosphere with a low oxygen concentration. The oxygen concentration is preferably 19% by volume or less, more preferably 15% by volume or less, even more preferably 10% by volume or less, particularly preferably 7% by volume or less, and most preferably 3% by volume or less. There is no particular lower limit, but a concentration of 10 ppm by volume or more is practical.

[0258] Moreover, instead of the post-baking by heating, the curing may be completed by UV (ultraviolet) irradiation. In this case, the magnetic particle-containing composition preferably further contains a UV curing agent. The UV curing agent is preferably a UV curing agent that can be cured at a wavelength shorter than 365 nm, which is the exposure wavelength of a polymerization initiator added for a lithography process using normal i-line exposure. Examples of the UV curing agent include Omnirad 2959 (trade name) (manufactured by IGM Resins BV). In the case of performing UV irradiation, it is preferable that the composition layer is a material that is cured at a wavelength of 340 nm or less. There is no particular lower limit of the wavelength, but it is generally 220 nm or more. The exposure dose of UV irradiation is preferably 100 to 5000 mJ, more preferably 300 to 4000 mJ, and even more preferably 800 to 3500 mJ. It is preferable to perform this UV curing process after the exposure treatment in order to perform low-temperature curing more effectively. It is preferable to use an ozone-free mercury lamp as the exposure light source.

[0259] [Electronic components] The electronic component of the present invention includes the above-mentioned magnetic particle-containing film of the present invention. That is, the electronic component of the present invention may include the above-mentioned magnetic particle-containing film as a part of the component. Examples of the electronic component include an inductor and an antenna. The electronic component may have a known structure. EXAMPLES

[0260] The present invention will be described in more detail below based on examples. The materials, amounts, ratios, processing contents, and processing procedures shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the following examples.

[0261] [Various components used in the preparation of the magnetic particle-containing composition] In preparing the magnetic particle-containing composition, the components shown in Table 1 were prepared. The outline of each component shown in Table 1 is shown below.

[0262] [Magnetic particles] M-1: Fe-based amorphous particles (product name "AW2-08 PF-5F", manufactured by Epson Atmix, average primary particle diameter 3 μm) M-2: Fe-based amorphous particles (product name "AW2-08 PF-8F", manufactured by Epson Atmix, average primary particle diameter 5 μm) M-3: Fe-Si-Cr alloy particles (product name "MA-XCQ-4", manufactured by DOWA Electronics, average primary particle diameter 3 μm) M-4: Fe-Si-Cr alloy particles (product name "MA-XCQ-5", manufactured by DOWA Electronics, average primary particle diameter 5 μm) M-5: Fe-based amorphous particles (product name "KUAMET6B2-V1-38μm", manufactured by Epson Atmix, average primary particle diameter 15μm) M-6: Fe-based amorphous particles (product name "KUAMET6B2-53μm", manufactured by Epson Atmix, average primary particle diameter 24μm) M-7: Fe-based amorphous particles (product name "KUAMET6B2-150μm", manufactured by Epson Atmix, average primary particle diameter 50μm) M-8: Co-based amorphous particles (product name "KUAMET-CT5-25μm", manufactured by Epson Atmix, average primary particle diameter 25μm) M-9: Co-based amorphous particles (product name "KUAMET-CT5-5μm", manufactured by Epson Atmix, average primary particle diameter 5μm) M-10: Supermalloy particles (product name "80%NI-4MO WA13", manufactured by Epson Atmix, average primary particle diameter 15 μm) M-11: Supermalloy particles (product name "80%NI-4MO PF-15F", manufactured by Epson Atmix, average primary particle diameter 8 μm) M-12: Supermalloy particles (product name "80%NI-4MO PF-5F", manufactured by Epson Atmix, average primary particle diameter 4 μm) M-13: Ni-Zn ferrite particles (product name "BSN-125", Toda Kogyo Co., Ltd., average primary particle diameter 5 μm) M-14: Mn-Zn ferrite particles (product name "BSF-547", Toda Kogyo Co., Ltd., average primary particle diameter 11 μm) M-15: Ni-Zn ferrite particles (product name "NB4", manufactured by Japan Metals and Chemicals Co., Ltd., average primary particle diameter 3 μm) M-16: Magnetoplumbite-type hexagonal ferrite particles (SrFe (9.58) Al (2.42) O 19 , produced in the same manner as described in Example 1 of WO 2019 / 131675, crystal phase is single layer, average primary particle size is 0.1 μm) M-17: Magnetoplumbite-type hexagonal ferrite particles (SrFe (9.58) Al (2.42) O 19 , produced in the same manner as described in Example 1 of WO 2019 / 131675, crystal phase is single layer, average primary particle size is 5 μm) M-18: Magnetoplumbite-type hexagonal ferrite particles (SrFe (9.58) Al (2.42) O 19 , produced in the same manner as described in Example 1 of WO 2019 / 131675, crystal phase is single layer, average primary particle size is 15 μm)

[0263] The average primary particle diameters of the magnetic particles are all values ​​measured by the method described above.

[0264] [Resin (dispersant)] D-1: The following compound (weight average molecular weight 10,000, amine value 50 mgKOH / g, acid value 50 mgKOH / g, solubility in solvent S-1 300 g / L, solubility in solvent S-2 300 g / L) D-2: The following compound (weight average molecular weight 10,000, solubility in solvent S-1 300 g / L, solubility in solvent S-2 300 g / L, acid value 70 mg KOH / g) D-3: The following compound (weight average molecular weight 10,000, acid value 40 mgKOH / g, solubility in solvent S-1 400 g / L, solubility in solvent S-2 400 g / L) D-4: Product name "BYK-P105" (manufactured by BYK), low molecular weight unsaturated carboxylic acid polymer, acid value 365 mg KOH / g, solubility in solvent S-1 500 g / L, solubility in solvent S-2 500 g / L D-5: Product name "ANTI-TERRA-204" (manufactured by BYK), solution of polycarboxylate of polyaminoamide, amine value 37 mg KOH / g, acid value 41 mg KOH / g, solubility in solvent S-1 300 g / L, solubility in solvent S-2 300 g / L D-6: Product name "Talen VA-705B" (Kyoeisha Chemical Co., Ltd.), higher fatty acid amide, solubility in solvent S-1 100g / L, solubility in solvent S-2 100g / L D-7: Product name "FLOWNON RCM-300TL" (Kyoeisha Chemical Co., Ltd.), higher fatty acid amide, solubility in solvent S-1 100g / L, solubility in solvent S-2 100g / L D-8: The following compound

[0265] [ka]

[0266] [ka]

[0267] [ka]

[0268] [ka]

[0269] 〔solvent〕 S-1: Propylene glycol monomethyl ether acetate (PGMEA), boiling point 146°C S-2: 1,4-butanediol diacetate (1,4-BDDA), boiling point 232°C

[0270] [Other ingredients] A-1: Curing accelerator (triphenylphosphine, manufactured by Tokyo Chemical Industry Co., Ltd.) A-2: Photopolymerization initiator (product name "IRGACURE-OXE03", manufactured by BASF) A-3: Polymerizable compound (product name "KAYARAD RP-1040", manufactured by Nippon Kayaku Co., Ltd., multifunctional acrylic monomer) A-4: Polymerizable compound (product name "Celloxide 2021P", Daicel Corporation, multifunctional epoxy monomer) A-5: Polymerizable compound (product name "Denacol EX-614", Nagase ChemteX Corporation, multifunctional epoxy monomer) A-6: Photopolymerization initiator (product name "ADEKA ARCLES NCI-831", manufactured by ADEKA Corporation) A-7: Polymerizable compound (product name "A-TMMT", Toagosei Co., Ltd., polyfunctional acrylic monomer)

[0271] [Preparation of magnetic particle-containing compositions of examples and comparative examples] The components other than the solvent shown in Table 1 were mixed in the composition ratio (by mass) shown in Table 1 and placed in a sealed container made of PTFE (polytetrafluoroethylene). Next, a solvent was added to obtain the composition ratio (by mass) shown in Table 1, and the container was then sealed. A Resodyn RAM (low frequency resonant acoustic mixer) was used to disperse the mixture at 50 G for 2 hours, thereby preparing magnetic particle-containing compositions for each of the Examples and Comparative Examples.

[0272] <Physical properties of magnetic particle-containing composition> The particle size distribution curve representing the volume-based frequency distribution of the magnetic particle-containing composition was measured according to the method described above, and the Dmax (μm), Dmin (μm), and Dmax / Dmin of the magnetic particles contained in the magnetic particle-containing composition were determined. The results are shown in Table 1.

[0273] The viscosity of the magnetic particle-containing composition at 23° C. was measured according to the method described above. The viscosity was classified according to the following criteria based on the measured value. The results are shown in Table 1. (Speed ​​up condition: 0.1(1 / s)) A:50Pa·s or more B: 1 Pa s or more, less than 50 Pa s C: Less than 1 Pa·s (Speed ​​up condition: 1000(1 / s)) A: Less than 10 Pa·s B: 10 Pa s or more, less than 50 Pa s C:50Pa·s or more

[0274] [Production of films containing magnetic particles for magnetic permeability evaluation] The magnetic particle-containing composition obtained as described above was used to produce a magnetic particle-containing film for magnetic permeability evaluation, which will be described later. Specifically, each magnetic particle-containing composition was dropped onto a silicon wafer (film thickness 100 μm) (hereinafter also referred to as "Substrate A"), and then coated using a baker applicator so that the film would have a film thickness of 100 μm after baking as described below. After that, a dry bake was performed for 10 minutes using a hot plate at 100° C., and then a hardening bake was performed for 15 minutes using a hot plate at 230° C., to obtain a magnetic particle-containing film for magnetic permeability evaluation. However, when the magnetic particle-containing composition contains a photopolymerization initiator, the curing is performed by applying 20 J / cm 2 using a UV (ultraviolet) cure device (manufactured by Ushio Inc.) instead of the curing bake. 2 The entire surface of the coating film was exposed to light at an exposure amount of 1000 nm to obtain a magnetic particle-containing film for evaluating magnetic permeability.

[0275] [Production of magnetic particle-containing films for pattern shape evaluation] Of the magnetic particle-containing compositions obtained as described above, a magnetic particle-containing film for pattern shape evaluation, which will be described later, was produced from the magnetic particle-containing composition containing a photopolymerization initiator. Specifically, each magnetic particle-containing composition was dropped onto a silicon wafer (film thickness 700 μm) (hereinafter also referred to as "Substrate B") with an undercoat layer (manufactured by Fujifilm Electronic Materials Co., Ltd., CT-4000L, thickness 0.1 μm), and then coated using a baker applicator so that the film thickness would be 30 μm after baking as described below. Thereafter, a dry bake was performed for 10 minutes using a hot plate at 100° C. to obtain a dry film. Next, the pattern is exposed through a mask with a line and space pattern (line width 300 μm, space width 300 μm) at 100 mJ / cm using a proximity exposure machine. 2 The dried film was exposed to light under the following conditions. After exposure, a shower development process was carried out for 60 seconds at 23° C. using a simple developing device (manufactured by Mikasa Co., Ltd.) Note that the developing solution used was an aqueous solution containing 0.3 mass % of tetramethylammonium hydroxide (TMAH). After development, a rinsing treatment was performed by spin shower using pure water, and then the resist was spin-dried, and then a heat treatment (post-baking) was performed for 5 minutes using a hot plate at 200°C. In this manner, a magnetic particle-containing film for pattern shape evaluation was obtained.

[0276] [Evaluation test] [Sedimentation stability (temporal stability)] 3 mL of the magnetic particle-containing composition obtained as described above was placed in a glass sample bottle (cylindrical, diameter 23 mm×height 35 mm), sealed, and then allowed to stand at 25° C. for 30 days. Thereafter, the magnetic particle-containing composition in the sample bottle was visually observed, and the distance d1 from the gas-liquid interface to the interface between the transparent region and the opaque region, and the distance d2 from the gas-liquid interface to the bottom of the sample bottle were measured. Using the distances d1 and d2, the sedimentation stability was evaluated according to the following criteria. If the following criteria was "2" or higher, it was determined that the sedimentation stability was excellent. The results are shown in Table 1. 3: d1 / d2=0 2: 0.4≧d1 / d2>0 1: d1 / d2>0.4

[0277] [Magnetic permeability] The magnetic particle-containing film for magnetic permeability evaluation obtained as described above was cut into a size of 10 mm x 28 mm. The relative magnetic permeability μ' at 100 MHz of the cut samples was measured using a high-frequency magnetic permeability measuring device (Keycom Co., Ltd., Model No. PER01) and evaluated based on the following evaluation criteria. If the following evaluation criteria was "3" or higher, it was determined that the magnetic permeability was excellent. The results are shown in Table 1. 5: Relative permeability μ' is 20 or more 4: Relative permeability μ' is 15 or more and less than 20 3: Relative permeability μ' is 10 or more and less than 15 2: Relative magnetic permeability μ' is 5 or more and less than 10 1: Relative permeability μ' is 1 or more and less than 5

[0278] [Pattern shape] The magnetic particle-containing film for pattern shape evaluation obtained as described above was observed using an optical microscope (product name "BX53M", manufactured by Olympus Corporation), and the pattern shape was evaluated based on the following evaluation criteria. The results are shown in Table 1. 3: The line pattern is in close contact with the substrate, spaces are formed, and no residues larger than 50 μm exist. 2: The line pattern is in close contact with the substrate and spaces are formed, but residues of 50 μm or more in size are present in the spaces. 1: The line pattern is not in close contact with the board, or the space is filled (no space exists).

[0279] [Table 1]

[0280] [Table 2]

[0281] [Table 3]

[0282] [Table 4]

[0283] [Table 5]

[0284] [Table 6]

[0285] [Table 7]

[0286] As shown in Table 1, a magnetic particle-containing composition containing magnetic particles having multiple peak tops in a particle size distribution curve representing a volume-based frequency distribution, a resin, and a solvent had excellent sedimentation stability, and a magnetic particle-containing film formed using this had excellent magnetic permeability (Example).

[0287] Comparison of Examples 1 to 12 shows that if Dmax / Dmin exceeds 2 (Examples 1 to 9, 11, and 12), the magnetic particle-containing film formed using this has superior magnetic permeability. Comparison with Example 3 and Examples 21 to 24 shows that the use of a resin having an acid group, a basic group or an amide group (Examples 21 to 24) results in superior sedimentation stability of the magnetic particle-containing composition. A comparison of Examples 50 to 55 shows that when the content of magnetic particles is 60 mass% or more relative to the total mass of the magnetic particle-containing composition (Examples 50, 51 and 53), it is possible to achieve a higher level of both the sedimentation stability of the magnetic particle-containing composition and the magnetic permeability of the magnetic particle-containing film.

[0288] On the other hand, when there is only one peak top in the particle size distribution curve representing the volume-based frequency distribution of the magnetic particles contained in the magnetic particle-containing composition, it has been shown that at least one of the sedimentation stability of the magnetic particle-containing composition and the magnetic permeability of the magnetic particle-containing film formed using the same is inferior (comparative example).

Claims

1. A magnetic particle-containing composition comprising magnetic particles having a plurality of peak tops in a particle size distribution curve representing a volume-based frequency distribution, a resin, and a solvent, The magnetic particle-containing composition further contains a polymerizable compound, The polymerizable compound is a magnetic particle-containing composition containing two or more types of compounds having an epoxy group.

2. The magnetic particle-containing composition described in claim 1, wherein the compound having an epoxy group is a multifunctional epoxy monomer.

3. A magnetic particle-containing composition described in claim 1 or 2, wherein the content of the polymerizable compound is 1 to 25 mass % relative to the total solid content of the magnetic particle-containing composition.

4. Among the plurality of peak tops in a particle size distribution curve representing the volume-based frequency distribution, the particle diameter at the peak top Pmin having the smallest particle diameter is defined as Dmin, and the particle diameter at the peak top Pmax having the largest particle diameter is defined as Dmax.

4. The magnetic particle-containing composition according to claim 1, wherein the ratio of Dmax to Dmin is greater than 2.

5. When the particle diameter at the peak top Pmin having the smallest particle diameter among the plurality of peak tops in the particle size distribution curve representing the volume-based frequency distribution is defined as Dmin, The Dmin is the particle diameter D at which the frequency is 20% in a particle size distribution curve representing a cumulative distribution on a volume basis. 20 The magnetic particle-containing composition according to any one of claims 1 to 4, wherein

6. 6. The magnetic particle-containing composition according to claim 4, wherein the Dmin is 1 to 10 μm.

7. 7. The magnetic particle-containing composition according to claim 1, wherein the magnetic particles have two peak tops.

8. 8. The magnetic particle-containing composition according to claim 1, wherein the content of the magnetic particles is 60 mass % or more based on the total mass of the magnetic particle-containing composition.

9. 9. The magnetic particle-containing composition according to claim 1, wherein the resin has an acid group, a basic group or an amide group.

10. 10. The magnetic particle-containing composition according to claim 1, wherein the solubility of the resin in the solvent is 10 g / L or more.

11. A magnetic particle-containing film formed by using the magnetic particle-containing composition according to any one of claims 1 to 10.

12. An electronic component comprising the magnetic particle-containing film according to claim 11.

13. 13. The electronic component according to claim 12, used as an inductor.

14. The electronic component according to claim 12, which is used as an antenna.